Crosslinked rubber composition, rubber composition for tire, molded body for tire side, sheet, method for manufacturing tire side, tire side

CN116761727BActive Publication Date: 2026-10-23ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 17 Cites 0 Cited by

Patent Information

Application Number
CN202180087236.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-04-07
Filing Date
2021-12-22
Publication Date
2026-10-23
Estimated Expiration
2041-12-22

AI Technical Summary

Benefits of technology

[0053]根据本发明,可得到机械强度高、用于轮胎部件后的省油耗性高、臭氧耐性高的交联用橡胶组合物。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention provides a crosslinking rubber composition containing a rubbery polymer (A) and a crosslinking agent (B), the rubbery polymer (A) having an iodine value of 10 to 250 (g / 100 g), an ethylene structure of ³ 3 mass%, a vinyl aromatic monomer block of < 10 mass%, containing a nitrogen atom, and a modification rate of 40 mass% or more as measured by a column adsorption GPC method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to crosslinking rubber compositions, tire rubber compositions, molded articles for tire sidewalls, sheets, methods for manufacturing tire sidewalls, and tire sidewalls. Background Technology

[0002] Previously, as a material for tire components, in order to improve mechanical strength and reduce compression set, a crosslinking rubber composition was proposed, which contains a rubber-like polymer having an ethylene structure and incorporating crosslinkable unsaturated groups (see, for example, Patent Documents 1-5).

[0003] Existing technical documents

[0004] Patent documents

[0005] Patent Document 1: International Publication No. 2003 / 085010

[0006] Patent Document 2: Japanese Patent Application Publication No. 2010-270314

[0007] Patent Document 3: International Publication No. 2019 / 151126

[0008] Patent Document 4: International Publication No. 2019 / 151127

[0009] Patent Document 5: International Publication No. 2019 / 078083 Summary of the Invention

[0010] The problem that the invention aims to solve

[0011] However, the crosslinking rubber compositions previously proposed, which contain rubber-like polymers with ethylene structures and crosslinkable unsaturated groups, have the following problems: their mechanical strength, fuel efficiency when used in tire components, and ozone resistance have not been adequately achieved, and there is still room for improvement.

[0012] Therefore, the object of the present invention is to provide a crosslinking rubber composition with high mechanical strength, high fuel efficiency and high ozone resistance when used in tire components.

[0013] Methods for solving problems

[0014] In order to solve the problems of the prior art, the inventors conducted in-depth research and found that the following crosslinking rubber composition containing a rubber-like polymer (A) and a crosslinking agent (B) can solve the problems of the prior art, thus completing the present invention. The iodine value, ethylene structure and vinyl aromatic monomer block content of the rubber-like polymer (A) are each within a specific numerical range, and the modification rate is within a specific numerical range.

[0015] That is, the present invention is as follows. [1]

[0017] A crosslinking rubber composition comprising: A rubbery polymer (A) with an iodine value of 10–250 (g / 100g), ethylene structure ≥3% by mass, vinyl aromatic monomer blocks <10% by mass, containing nitrogen atoms, and a modification rate of ≥40% by mass as determined by column adsorption GPC; and Crosslinking agent (B). [2]

[0019] The crosslinking rubber composition described in [1] above, wherein the rubber polymer (A) contains less than 35% by mass of vinyl aromatic monomer units. [3]

[0021] The crosslinking rubber composition as described in [1] or [2] above, wherein the content of vinyl units and butene units in the rubber-like polymer (A) is 20 mol% or more. [4]

[0023] A rubber composition for tires, comprising any one of the crosslinking rubber compositions described in [1] to [3] above, comprising: The rubber component, comprising 30 parts by mass or more of natural rubber and 10 parts by mass or more of the aforementioned rubbery polymer (A) per 100 parts by mass; and The above-mentioned crosslinking agent (B). [5]

[0025] The tire rubber composition described in [4] above, wherein the content of the rubber polymer (A) in 100 parts by mass of the rubber component is 30 parts by mass or more. [6]

[0027] The tire rubber composition described in [4] or [5] above further contains a nitrogen adsorption specific surface area (N2SA) of 20 to 150 m². 2 The specific surface area (N2SA) of carbon black and / or nitrogen adsorption per gram is 110–220 m². 2 / g of silica-based inorganic filler. [7]

[0029] The tire rubber composition described above [6] contains: 100 parts by weight of rubber component, comprising 30 parts by weight or more of natural rubber and 10 parts by weight or more of the above-mentioned rubbery polymer (A); 30–90 parts by mass, with a nitrogen adsorption specific surface area (N2SA) of 20–150 m². 2 The specific surface area (N2SA) of carbon black and / or nitrogen adsorption per gram is 110–220 m². 2 / g of silica-based inorganic filler; and The above-mentioned crosslinking agent (B). [8]

[0031] A molded body for tire sidewalls, comprising the crosslinking rubber composition described in any one of [1] to [3] above, comprising: 100 parts by weight of rubber component, which contains more than 30 parts by weight of natural rubber and more than 10 parts by weight of the above-mentioned rubbery polymer (A); 30–70 parts by mass, with a nitrogen adsorption specific surface area (N2SA) of 20–150 m². 2 The specific surface area (N2SA) of carbon black and / or nitrogen adsorption per gram is 110–220 m². 2 / g of silica-based inorganic filler; and The above-mentioned crosslinking agent (B). [9]

[0033] A sheet material comprising the crosslinking rubber composition described in any one of [1] to [3] above, wherein, The glass transition temperature of the rubbery polymer (A) is below -60°C, and the weight-average molecular weight is above 200,000.

[10]

[0035] The sheet described above [9] contains a rubber component, wherein 100 parts by weight of the rubber component includes more than 30 parts by weight of natural rubber, more than 10 parts by weight of butadiene rubber, and more than 10 parts by weight of the aforementioned rubbery polymer (A).

[11]

[0037] The sheet material as described in [9] or

[10] above, wherein the content of the rubber polymer (A) in 100 parts by mass of the rubber component is 30 parts by mass or more.

[12]

[0039] The sheet material as described in any one of [9] to

[11] above, wherein, relative to 100 parts by mass of the rubber component, further contains 50 to 90 parts by mass of a nitrogen adsorption specific surface area (N2SA) of 20 to 150 m². 2 The specific surface area (N2SA) of carbon black and / or nitrogen adsorption per gram is 110–220 m². 2 / g of silica-based inorganic filler.

[13]

[0041] The sheet according to any one of the above [9] to

[12] , wherein the SP value of the rubbery polymer (A) and the glass transition temperature Tg satisfy: (-0.03×Tg+14.4)<SP value<(-0.03×Tg+15.4).

[14]

[0043] The sheet according to any one of the above [9] to

[13] , which is a sheet for a tire sidewall.

[15]

[0045] A method for manufacturing a tire sidewall, comprising the following steps: a step of kneading the crosslinkable rubber composition according to any one of the above [1] to [3], natural rubber and butadiene rubber in such a manner that the content of the natural rubber is 30 parts by mass or more, the content of the butadiene rubber is 10 parts by mass or more, and the content of the rubbery polymer (A) is 10 parts by mass or more, based on 100 parts by mass of the rubber component; a step of forming into a sheet shape; and a step of crosslinking the obtained sheet-shaped molded body.

[16]

[0047] A tire sidewall, comprising: 10 parts by mass or more of a rubbery polymer (A), wherein the rubbery polymer (A) has an iodine value of 10 to 250 (g / 100g), an ethylene structure content of ≧3% by mass, a vinyl aromatic monomer block content of <10% by mass, contains a nitrogen atom, has a modification rate of 40% by mass or more as measured by column adsorption GPC, a glass transition temperature of -60°C or lower, and a weight average molecular weight of 200,000 or more; 30 parts by mass or more of natural rubber; and 10 parts by mass or more of butadiene rubber, wherein the tire sidewall has a structure formed by crosslinking the rubbery polymer (A), the natural rubber and the butadiene rubber.

[17]

[0049] The tire sidewall according to the above

[16] , wherein the SP value of the rubbery polymer (A) and the glass transition temperature Tg satisfy: (-0.03×Tg+14.4)<SP value<(-0.03×Tg+15.4).

[18]

[0051] The tire sidewall according to the above

[16] or

[17] , comprising: 100 parts by weight of rubber component, comprising 10 parts by weight of the above-mentioned rubbery polymer (A), 30 parts by weight of natural rubber and 10 parts by weight of butadiene rubber; 50–90 parts by mass, with a nitrogen adsorption specific surface area (N2SA) of 20–150 m². 2 The specific surface area (N2SA) of carbon black and / or nitrogen adsorption per gram is 110–220 m². 2 / g of silica-based inorganic filler; and The above-mentioned crosslinking agent (B).

[0052] The effects of the invention

[0053] According to the present invention, a crosslinking rubber composition with high mechanical strength, high fuel efficiency when used in tire components, and high ozone resistance can be obtained. Detailed Implementation

[0054] The specific embodiments of the present invention (hereinafter referred to as "this embodiment") will be described in detail below.

[0055] It should be noted that the following embodiments are illustrative of the present invention, and the present invention is not limited to the following embodiments. The present invention can be suitably modified within the scope of its essential points.

[0056] [Rubber Composition for Crosslinking]

[0057] The crosslinking rubber composition of this embodiment contains a rubber-like polymer (A) and a crosslinking agent (B). The rubber-like polymer (A) has an iodine value of 10 to 250 (g / 100g), an ethylene structure of ≥3% by mass, a vinyl aromatic monomer block of <10% by mass, contains nitrogen atoms, and has a modification rate of ≥40% by mass as determined by column adsorption GPC method.

[0058] With the above configuration, a crosslinked rubber composition with high mechanical strength, high fuel efficiency when used in tire components, and high ozone resistance can be obtained.

[0059] (Rubber-like polymer (A))

[0060] The rubber-like polymer (A) contained in the crosslinking rubber composition of this embodiment has an iodine value of 10 to 250 (g / 100g), ethylene structure ≥3% by mass, vinyl aromatic monomer block <10% by mass, contains nitrogen atoms, and has a modification rate of 40% by mass or more as determined by column adsorption GPC method.

[0061] Iodine value

[0062] The iodine value of the rubbery polymer (A) is 10–250 (g / 100g).

[0063] From the perspective of the co-crosslinking property when the rubber-like polymer (A) is used in a crosslinking rubber composition, and the softness of the aforementioned tire material when used in a tire material, the iodine value is 10 (g / 100g) or more, preferably 15 (g / 100g) or more, more preferably 30 (g / 100g) or more, and even more preferably 50 (g / 100g) or more.

[0064] On the other hand, from the perspective of the high tensile strength and wear resistance of the material used in the tire, the iodine value is 250 (g / 100g) or less, preferably 200 (g / 100g) or less, more preferably 150 (g / 100g) or less, further preferably 100 (g / 100g) or less, and even more preferably 70 (g / 100g) or less.

[0065] Iodine value can be determined according to the method described in "JIS K 0070:1992".

[0066] The iodine value is a value expressed in grams of iodine, which is the amount of halogen that reacts with 100g of a substance. Therefore, the unit of iodine value is "g / 100g".

[0067] For example, in the method for manufacturing the rubber-like polymer described later, when the conjugated diene compound is copolymerized with a vinyl aromatic compound, the iodine value of the rubber-like polymer is low when the content of the conjugated diene monomer unit is low because the conjugated diene compound has a double bond; in addition, when the conjugated diene monomer unit is hydrogenated, the iodine value decreases when the hydrogenation rate is high.

[0068] The iodine value of the rubbery polymer can be controlled within the above-mentioned range by adjusting the amount of conjugated diene compounds with unsaturated bonds, polymerization time, polymerization temperature and other polymerization conditions, as well as the amount of hydrogenation and hydrogenation time in the hydrogenation process.

[0069] <Content of ethylene structure>

[0070] The rubber-like polymer (A) used in the crosslinking rubber composition of this embodiment has an ethylene content of 3% by mass or more. That is, an ethylene content ≥ 3% by mass.

[0071] By ensuring that the ethylene content of the rubber-like polymer (A) is 3% or more by mass, the tensile strength of the crosslinking rubber composition using the rubber-like polymer (A) is less likely to decrease. Preferably, the ethylene content is 5% or more by mass, more preferably 20% or more by mass, and even more preferably 40% or more by mass.

[0072] Furthermore, the ethylene content is preferably 90% by mass or less, more preferably 80% by mass or less, even more preferably 70% by mass or less, and even more preferably 60% by mass or less. By making the ethylene content in the rubbery polymer (A) 90% by mass or less, excellent rubber elasticity can be obtained.

[0073] The ethylene structure in the rubbery polymer (A) includes all ethylene structures obtained by polymerizing ethylene monomers, ethylene structures obtained by hydrogenating conjugated diene monomers, and so on. For example, hydrogenating a 1,4-butadiene unit yields two ethylene structures, and hydrogenating a 1,4-isoprene unit yields a propylene structure and an ethylene structure.

[0074] The ethylene structure of the rubbery polymer (A) can be determined by the method described in the examples below, and can be controlled within the above-mentioned numerical range by adjusting the amount of ethylene added, the amount of conjugated diene compound added, and the hydrogenation rate.

[0075] <Vinyl Aromatic Monomer Block Content>

[0076] In the rubber-like polymer (A) used in the crosslinking rubber composition of this embodiment, the content of vinyl aromatic monomer blocks is less than 10% by mass, that is, vinyl aromatic monomer blocks < 10% by mass.

[0077] Vinyl aromatic monomer blocks refer to blocks composed of eight or more vinyl aromatic monomer units linked together.

[0078] When the content of vinyl aromatic monomer blocks in the rubber-like polymer (A) is less than 10% by mass, the crosslinking rubber composition of this embodiment tends to easily improve fuel efficiency when used as a tire raw material.

[0079] The vinyl aromatic monomer block content of the rubber-like polymer (A) is preferably 7% by mass or less, more preferably 5% by mass or less, and even more preferably 3% by mass or less.

[0080] In the vinyl aromatic monomer blocks, from the perspective of the softness of the crosslinking rubber composition of this embodiment, it is preferable that the number of blocks formed by linking more than 30 vinyl aromatic monomer units is small or non-existent.

[0081] Regarding the morphology of the vinyl aromatic monomer blocks, specifically, in the case of a butadiene-styrene copolymer, the copolymer can be decomposed using the Kolthoff method (described in IM KOLTHOFF, et al., J. Polym. Sci. 1, 429 (1946)) to determine the amount of polystyrene insoluble in methanol, thereby performing the analysis. Alternatively, as described in International Publication No. 2014-133097, known methods such as determining the chain length of styrene units using NMR can be used for analysis.

[0082] The content of vinyl aromatic monomer blocks in the rubbery polymer (A) can be controlled within the above-mentioned range by adjusting the method of adding vinyl aromatic compounds, the amount of polymerization aids added, the polymerization temperature, etc.

[0083] <Monomer units that make the rubbery polymer (A) contain unsaturated groups>

[0084] The rubber-like polymer (A) used in the crosslinking rubber composition of this embodiment preferably contains 2% by mass or more of conjugated diene monomer units, myrcene, or other monomer units with unsaturated groups.

[0085] From an economic and manufacturing perspective, the rubber-like polymer (A) is more preferably found to contain conjugated diene monomer units.

[0086] When the rubber polymer (A) contains conjugated diene monomer units and myrcene as components, the resulting rubber polymer (A) also contains double bonds due to the double bonds of the conjugated diene monomer units and myrcene, thus becoming crosslinkable unsaturated groups.

[0087] The content of unsaturated monomer units such as conjugated diene monomer units and myrcene in the rubbery polymer (A) is closely related to the iodine value mentioned above.

[0088] It is preferable to have a content of 2% by mass or more of monomer units with unsaturated groups, such as conjugated diene monomer units and myrcene, for ease of crosslinking. More preferably, the content of conjugated diene monomer units is 3% by mass or more, and even more preferably 6% by mass or more.

[0089] Furthermore, the content of monomer units with unsaturated groups, such as conjugated diene monomer units and myrcene, is preferably 50% by mass or less, more preferably 30% by mass or less, and even more preferably 20% by mass or less. By setting the content of the aforementioned monomer units with unsaturated groups to 50% by mass or less, the crosslinking rubber composition of this embodiment exhibits excellent weather resistance and resistance to long-term degradation.

[0090] The content of conjugated diene monomer units, myrcene and other monomer units with unsaturated groups in the rubber-like polymer (A) can be determined by the "hydrogenation rate" determination method described in the following examples. In the manufacturing process of the rubber-like polymer (A), the above-mentioned numerical range can be controlled by adjusting the amount of added conjugated diene monomer units, myrcene and other monomers with unsaturated groups, and the hydrogenation rate.

[0091] <Content of α-olefin in rubbery polymer (A)>

[0092] From the perspective of the productivity of the rubber-like polymer (A), the content of α-olefins in all monomer units other than the vinyl aromatic monomer units in the rubber-like polymer (A) is preferably 13% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more.

[0093] On the other hand, from the perspective of the mechanical strength of the tire material after the crosslinking rubber composition is used in the tire material, the content of the α-olefin is preferably 70% by mass or less, more preferably 60% by mass or less, further preferably 55% by mass or less, and even more preferably 50% by mass or less.

[0094] The content of the α-olefin can be controlled by adjusting the content of the conjugated diene monomer units, the amount of vinyl binding, and the hydrogenation rate before hydrogenation when manufacturing a rubber-like polymer (A) by hydrogenating a polymer or copolymer of a conjugated diene compound.

[0095] It should be noted that when 1,2-butadiene is hydrogenated, it forms butene, becoming an α-olefin structure.

[0096] The α-olefin content of the rubbery polymer (A) can be determined by the methods described in the examples below. 1 The measurements were performed using H-NMR.

[0097] <Content of vinyl aromatic monomer units in rubber-like polymer (A)>

[0098] From the perspective of the deformation resistance of the molded body of the crosslinking rubber composition of this embodiment during transportation, and the breaking strength and wet skid resistance of the tire components after the crosslinking rubber composition of this embodiment is used in the tire tread and other tire component materials, the content of vinyl aromatic monomer units in the rubber-like polymer (A) used in the crosslinking rubber composition of this embodiment is preferably 5% by mass or more, more preferably 10% by mass or more, further preferably 15% by mass or more, and even more preferably 20% by mass or more.

[0099] On the other hand, from the perspective of the cutability of sheet or block molded bodies during measurement, the tightness of packaging films, and the resistance of packaging films to breakage, and further from the perspective of the fuel efficiency and wear resistance of the tires after using the crosslinking rubber composition of this embodiment in tire tread and other tire component materials, the content of vinyl aromatic monomer units in the rubber polymer (A) is preferably 45% by mass or less, more preferably 35% by mass or less, and even more preferably 25% by mass or less.

[0100] Furthermore, when the crosslinking rubber composition of this embodiment contains the hydrogenated resin (C) described later, from the perspective of the compatibility between the rubber polymer (A) and the hydrogenated resin (C), the content of the aromatic monomer unit is more preferably less than 30% by mass, and even more preferably less than 25% by mass.

[0101] The content of vinyl aromatic monomer units in the rubbery polymer (A) can be determined by the method described in the examples below, and can be controlled within the above-mentioned value range by adjusting the amount of vinyl aromatic compounds added in the polymerization process.

[0102] <Content of vinyl and butene units in rubber-like polymer (A)>

[0103] In the rubber-like polymer (A) used in the crosslinking rubber composition of this embodiment, the content of vinyl units and butene units is preferably 20 mol% or more.

[0104] From the perspectives of the manufacturability of the rubber-like polymer (A), the processability of the crosslinking rubber composition of this embodiment, and the anti-skid properties of the tire tread after being used as a material, the content of vinyl units and butene units is preferably 20 mol% or more, more preferably 25 mol% or more, and even more preferably 30 mol% or more. Furthermore, from the perspectives of the heat aging resistance of the rubber-like polymer (A) and the fuel efficiency of the tire tread after being used as a material, the content is preferably 60 mol% or less, more preferably 50 mol% or less, and even more preferably 45 mol% or less.

[0105] The content of vinyl units and butene units in the rubbery polymer (A) can be determined by the methods described in the examples below. 1 The determination was performed using H-NMR.

[0106] The content of vinyl units and butene units in the rubber-like polymer (A) can be controlled within the above-mentioned range by adjusting the amount of polar compounds added and the polymerization temperature in the polymerization process of the rubber-like polymer (A).

[0107] <Modification of rubber-like polymer (A)>

[0108] In the crosslinking rubber composition of this embodiment, from the perspective of peel resistance of the crosslinking rubber composition in the molded body of the crosslinking rubber composition and the fuel-saving properties of the tire after being used as a tire material, the rubber polymer (A) contains nitrogen atoms.

[0109] Regarding the rubber-like polymer (A) used in the crosslinking rubber composition of this embodiment, from the perspective of the mechanical strength of the crosslinking rubber composition and the dispersibility of the fillers such as silica and carbon black when it is used as a tire material, the modification rate of the rubber-like polymer (A) as determined by column adsorption GPC is 40% by mass or more. The modification rate of the rubber-like polymer (A) is preferably 60% by mass or more, and more preferably 70% by mass or more.

[0110] In this specification, "modification rate" refers to the mass ratio of the polymer with nitrogen-containing functional groups to the total amount of the rubbery polymer (A).

[0111] The nitrogen atom can be introduced into the rubber-like polymer (A) used in the crosslinking rubber composition of this embodiment at any position at the polymerization initiation end, in the molecular chain (including grafted products), or at the polymerization end of the rubber-like polymer (A).

[0112] The modification rate of the rubbery polymer (A) can be controlled within the above-mentioned range by adjusting the amount of modifier added to the rubbery polymer (A) and the modification process time.

[0113] When manufacturing the rubber-like polymer (A) used in the crosslinking rubber composition of this embodiment by hydrogenation after polymerization of a conjugated diene compound, from the perspectives of polymerization productivity, high modification rate, wear resistance of the aforementioned tires after use in tire materials, and fuel efficiency, it is preferable to use a method that introduces tin or nitrogen atoms into the polymer using a coupling agent containing tin or nitrogen atoms. In particular, it is more preferable to use a method that introduces nitrogen atoms into the polymer using a coupling agent containing nitrogen atoms.

[0114] As coupling agents containing nitrogen atoms, isocyanate compounds, isothiocyanate compounds, isocyanuric acid derivatives, carbonyl compounds containing nitrogen groups, vinyl compounds containing nitrogen groups, epoxy compounds containing nitrogen groups, and alkoxysilane compounds containing nitrogen groups are preferred from the perspective of polymerization productivity and high modification rate.

[0115] As coupling agents containing nitrogen atoms, alkoxysilane compounds containing nitrogen groups are more preferred from the aspects of polymerization productivity of rubber-like polymer (A), high modification rate, and tensile strength of the aforementioned tire material after use in tire materials.

[0116] Examples of nitrogen-containing alkoxysilane compounds include, but are not limited to, 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silazane, 2,2-diethoxy-1-(3-triethoxysilylpropyl)-1-aza-2-silazane, 2,2-dimethoxy-1-(4-trimethoxysilylbutyl)-1-aza-2-silazane, 2,2-dimethoxy-1-(5-trimethoxysilylpentyl)-1-aza-2-silazaneheptane, and 2,2- Dimethoxy-1-(3-dimethoxymethylsilylpropyl)-1-aza-2-silazopentane, 2,2-diethoxy-1-(3-diethoxyethylsilylpropyl)-1-aza-2-silazopentane, 2-methoxy-2-methyl-1-(3-trimethoxysilylpropyl)-1-aza-2-silazopentane, 2-ethoxy-2-ethyl-1-(3-triethoxysilylpropyl)-1-aza-2-silazopentane, 2-methoxy-2-methyl-1-(3-dimethoxymethylsilylpropyl) 1-aza-2-silazopentane, and 2-ethoxy-2-ethyl-1-(3-diethoxyethylsilylpropyl)-1-aza-2-silazopentane, tris(3-trimethoxysilylpropyl)amine, tris(3-methyldimethoxysilylpropyl)amine, tris(3-triethoxysilylpropyl)amine, tris(3-methyldiethoxysilylpropyl)amine, tris(trimethoxysilylmethyl)amine, tris(2-trimethoxysilylethyl)amine, tris(4-trimethoxysilylbutyl)amine, tetra[3-( [2,2-Dimethoxy-1-aza-2-silazane-cyclopentane]-1,3-propanediamine, tetra(3-trimethoxysilylpropyl)-1,3-propanediamine, tetra(3-trimethoxysilylpropyl)-1,3-diaminomethylcyclohexane, and N1-(3-(bis(3-(trimethoxysilyl)propyl)amino)propyl)-N1-methyl-N3-(3-(methyl(3-(trimethoxysilyl)propyl)amino)propyl)-N3-(3-(trimethoxysilyl)propyl)-1,3-propanediamine, etc.

[0117] When the rubber-like polymer (A) used in the crosslinking rubber composition of this embodiment is manufactured by copolymerizing ethylene with a conjugated diene compound, from the perspective of the breaking strength of the crosslinking rubber composition of this embodiment, the fuel efficiency of the tire after it is used as a tire material, the wear resistance and the softness, the rubber-like polymer (A) preferably contains nitrogen atoms, and further contains tin atoms and silicon atoms.

[0118] From the perspective of the manufacturability of the rubber-like polymer (A), it is preferable to adopt the following method: when the conversion rate of the polymerization reaction reaches 100%, nitrogen atoms, tin atoms, and silicon atoms are introduced by using a coupling agent containing nitrogen atoms, and further by a coupling agent containing tin atoms and silicon atoms.

[0119] Examples of coupling agents containing nitrogen, tin, or silicon atoms include, but are not limited to, tin-containing compounds such as bis(1-octadecyl maleate) dioctyltin, isocyanate compounds such as 4,4-diphenylmethane diisocyanate, and alkoxysilane compounds such as glycidylpropyltrimethoxysilane.

[0120] <Glass transition temperature of rubbery polymer (A)>

[0121] From the perspective of the tensile strength of the crosslinking composition, the glass transition temperature of the rubber-like polymer (A) used in the crosslinking rubber composition of this embodiment is preferably -90°C or higher, more preferably -80°C or higher, and even more preferably -75°C or higher.

[0122] On the other hand, from the perspective of the softness of the crosslinking rubber composition and the fracture resistance of the sheet of the crosslinking rubber composition of this embodiment in the tire manufacturing process, it is preferable to be below -15°C, preferably below -30°C, and more preferably below -40°C.

[0123] Regarding the glass transition temperature of the rubbery polymer (A), according to ISO 22768:2006, the peak (inflection point) of the DSC differential curve when the temperature is increased within a specified temperature range while recording the DSC curve is taken as the glass transition temperature.

[0124] <Weight-average molecular weight of rubber-like polymer (A)>

[0125] From the perspectives of compatibility with materials such as the crosslinking agent (B) and the rubber components contained in the crosslinking rubber composition, and the elongation at break of the crosslinking rubber composition, the weight-average molecular weight of the rubber-like polymer (A) used in the crosslinking rubber composition of this embodiment is preferably 100,000 or more, more preferably 150,000 or more, further preferably 200,000 or more, and even more preferably 250,000 or more.

[0126] On the other hand, from the perspective of the processability of the crosslinking rubber composition, it is preferred to have 1 million or less, more preferably 700,000 or less, further preferably 600,000 or less, and even more preferably 500,000 or less.

[0127] From the perspective of compatibility with materials such as the crosslinking agent (B) and the rubber components contained in the crosslinking rubber composition, and the fuel-saving properties after use in tires, the molecular weight distribution (= weight average molecular weight / number average molecular weight) of the rubber-like polymer (A) is preferably 2.0 or less, more preferably 1.8 or less, and even more preferably 1.6 or less. On the other hand, from the perspective of the processability of the crosslinking rubber composition, it is preferably 1.05 or more, more preferably 1.2 or more, and even more preferably 1.4 or more.

[0128] The weight-average molecular weight and molecular weight distribution can be calculated based on the molecular weight of polystyrene determined by GPC (gel permeation chromatography).

[0129] The weight-average molecular weight and molecular weight distribution of the rubbery polymer (A) can be controlled within the above-mentioned range by adjusting various polymerization conditions such as the amount of monomer added, polymerization time, polymerization temperature, and polymerization pressure in the polymerization process.

[0130] The rubber-like polymer (A) used in the crosslinking rubber composition of this embodiment can have two or more polymer blocks with different ratios of vinyl aromatic monomers, ethylene, α-olefins, and conjugated diene monomers, from the perspective of compatibility with materials such as the crosslinking agent (B) and the rubber components contained in the crosslinking rubber composition, and from the perspective of obtaining appropriate softness of the crosslinking rubber composition over a wide range from low to high temperatures. From the perspective of softness, the amount of vinyl aromatic monomers in the polymer blocks is preferably 60% by mass or less, more preferably 50% by mass or less, and even more preferably 40% by mass or less.

[0131] <Hydrogenation rate of rubber-like polymer (A)>

[0132] From the perspective of balancing fuel efficiency and mechanical strength in the crosslinking rubber composition of this embodiment, the hydrogenation rate of the rubber polymer (A) used in the crosslinking rubber composition of this embodiment is preferably 60-95 mol%, more preferably 70-90 mol%, and even more preferably 75-85 mol%.

[0133] The hydrogenation rate of the rubbery polymer (A) can be determined by the method described in the examples below.

[0134] The hydrogenation rate can be controlled within the above-mentioned range by appropriately adjusting the conditions in the hydrogenation process.

[0135] <Method for manufacturing rubber-like polymer (A)>

[0136] The rubber-like polymer (A) used in the crosslinking rubber composition of this embodiment is preferably manufactured by polymerizing or copolymerizing at least a conjugated diene compound, followed by hydrogenation (hydrogenation) of a portion or most of the double bond; or by copolymerizing at least ethylene with a conjugated diene compound.

[0137] As a method for hydrogenating the double bond after polymerizing or copolymerizing the conjugated diene compound, examples include: as described in International Publication No. 96 / 05250, Japanese Patent Application Publication No. 2000-053706, International Publication No. 2003 / 085010, International Publication No. 2019 / 151126, International Publication No. 2019 / 151127, International Publication No. 2002 / 002663, and International Publication No. 2015 / 006179, in which various additives are added and various conditions are selected to polymerize the conjugated diene compound by anionic polymerization, and then hydrogenate it after copolymerizing it with other monomers as needed.

[0138] As a method for copolymerizing at least ethylene with a conjugated diene compound, examples include those described in International Publication Nos. 2019 / 078083, 2019 / 171679, and 2019 / 142501, in which various additives are added and various conditions are selected, and ethylene, the conjugated diene compound, and other monomers, if necessary, are added and copolymerized by coordination polymerization.

[0139] From the perspective of expanding the structural freedom of manufactureable rubber-like polymers, the rubber-like polymer (A) is preferably manufactured by hydrogenation after polymerization of a conjugated diene compound.

[0140] Examples of conjugated diene compounds include, but are not limited to, 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 3-methyl-1,3-pentadiene, 1,3-hexadiene, and 1,3-heptadiene.

[0141] Among these, 1,3-butadiene and isoprene are preferred from the perspective of ease of industrial acquisition, with 1,3-butadiene being more preferred.

[0142] They can be used individually or in combination with more than one type.

[0143] Other compounds besides conjugated diene compounds used to manufacture rubber-like polymers (A) include vinyl aromatic compounds.

[0144] Examples of vinyl aromatic compounds include, but are not limited to, styrene, p-methylstyrene, α-methylstyrene, vinyl ethylbenzene, vinyl xylene, vinyl naphthalene, diphenylethylene, vinyl benzyl dimethylamine, (4-vinylbenzyl)dimethylaminoethyl ether, N,N-dimethylaminoethylstyrene, N,N-dimethylaminomethylstyrene, and diphenylethylene containing a tertiary amino group (e.g., 1-(4-N,N-dimethylaminophenyl)-1-phenylethylene).

[0145] Of these, styrene is preferred from the perspective of ease of industrial acquisition.

[0146] They can be used individually or in combination with more than one type.

[0147] In addition to conjugated diene compounds and vinyl aromatic compounds, other monomers may be used as needed as compounds for manufacturing rubber-like polymers (A).

[0148] Other monomers include, but are not limited to, unsaturated carboxylic acid esters, unsaturated carboxylic acids, α,β-unsaturated nitrile compounds, α-olefins (butene, propylene, butene, pentene, hexene, etc.), ethylene, myrcene, ethylene-norbornene, isopropylidene-norbornene, cyclopentadiene, divinylbenzene, etc.

[0149] They can be used individually or in combination with more than one type.

[0150] When manufacturing the rubber-like polymer (A) used in the crosslinking rubber composition of this embodiment by hydrogenation after polymerization or copolymerization of a conjugated diene compound, it is important to adjust the vinyl content of the conjugated diene monomer units of the conjugated diene polymer before hydrogenation, considering the characteristics of the rubber-like polymer (A) and the characteristics of the crosslinking rubber composition of this embodiment. Regarding the vinyl content of the conjugated diene monomer units, from the perspective of the productivity of the rubber-like polymer (A) and the high anti-skid properties of the tires used as tire materials, the vinyl content is preferably 10 mol% or more, more preferably 20 mol% or more. In addition, from the perspective of the mechanical strength of the tires used as tire materials, it is preferably 75 mol% or less, more preferably 60 mol% or less, further preferably 45 mol% or less, and even more preferably 30 mol% or less.

[0151] The amount of vinyl bound can be determined by the method described in the examples below.

[0152] The polymerization and hydrogenation processes described above can be carried out in either a batch or continuous manner.

[0153] The hydrogenation rate of the rubbery polymer (A), and the intermolecular or intramolecular distribution of monomer units from ethylene, conjugated diene monomers, myrcene, α-olefins, and vinyl aromatic monomers are not particularly limited; they can be uniform, non-uniform, or have a distribution.

[0154] (Addition of additives to rubbery polymer (A))

[0155] The rubber-like polymer (A) used in the crosslinking rubber composition of this embodiment is preferably used in the crosslinking rubber composition of this embodiment with various additives added during its manufacturing process.

[0156] Rubber softener

[0157] In the rubber-like polymer (A), from the perspective of improving the productivity of the rubber-like polymer (A) and the processability when blending inorganic fillers during tire manufacturing, it is preferable to add 1 to 30% by mass of a rubber softener as an additive. When the molecular weight of the rubber-like polymer (A) is high, for example, when the weight-average molecular weight is greater than 1 million, it is preferable to use 15 to 30% by mass of a rubber softener; on the other hand, when blending fillers to form a rubber composition, in order to broaden the freedom of the blending amount of fillers, it is preferable to use 1 to 15% by mass of a rubber softener.

[0158] From the perspective of improving the tire's resistance to deterioration over time after being used in tire materials, the content of rubber softener in the crosslinking rubber composition of this embodiment, which includes rubber-like polymer (A), is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less.

[0159] There are no particular limitations on the type of softener used for rubber, such as filler oils, liquid rubbers and resins. However, filler oils are preferred from the perspectives of processability, productivity and economy.

[0160] As a method for adding a rubber softener to a rubber-like polymer (A), the preferred method is, but not limited to, the following: adding a rubber softener to a solution of rubber-like polymer (A), mixing to prepare a solution of rubber-like polymer (A) containing a rubber softener, and then desolvating it.

[0161] [Fill oil]

[0162] Examples of filler oils used as rubber softeners include aromatic oils, cycloalkane oils, and paraffinic oils.

[0163] Among these, from the perspectives of environmental safety, prevention of oil seepage, and wetland grip properties, alternative aromatic oils with a polycyclic aromatic (PCA) content of 3% by mass or less based on the IP346 method are preferred. Examples of alternative aromatic oils include TDAE (Treated Distillate Aromatic Extracts), MES (Mild Extraction Solvate), and RAE (Residual Aromatic Extracts), as shown in Kautschuk Gummi Kunststoffe 52(12)799(1999).

[0164] <Rubber Stabilizers>

[0165] In the rubber-like polymer (A) used in the crosslinking rubber composition of this embodiment, after its polymerization step, a rubber stabilizer is preferably added from the perspective of preventing gel formation and improving processing stability.

[0166] As stabilizers for rubber, examples include, but are not limited to, antioxidants such as 2,6-di-tert-butyl-4-hydroxytoluene (hereinafter also referred to as "BHT"), n-octadecyl-3-(4'-hydroxy-3',5'-di-tert-butylphenol) propionate, and 2-methyl-4,6-bis[(octylthio)methyl]phenol.

[0167] (Physical properties of rubber-like polymer (A))

[0168] <Residual solvent content>

[0169] In the crosslinking rubber composition of this embodiment, from the perspective of reducing odor and VOCs, it is preferable that the residual amount of polymerization solvent used in the polymerization process of the rubber-like polymer (A) is low. Specifically, it is preferably 5000 ppm or less, more preferably 3000 ppm or less, and even more preferably 1500 ppm or less. In addition, from the perspective of balancing the above-mentioned characteristics and economy, it is preferably 50 ppm or more, more preferably 150 ppm or more, and even more preferably 300 ppm or more.

[0170] Moisture content

[0171] The moisture content of the rubber-like polymer (A) used in the crosslinking rubber composition of this embodiment, the crosslinking agent (B) added (described later), and various additives is preferably 0.05% by mass or more and 1.5% by mass or less. From the viewpoint of suppressing gel formation during drying after removing the polymerization solvent, the moisture content of the crosslinking rubber composition is preferably 0.05% by mass or more, more preferably 0.1% by mass or more, and even more preferably 0.2% by mass or more. On the other hand, from the viewpoint of suppressing condensation and improving the colorfastness of the crosslinking rubber composition, this moisture content is preferably 1.5% by mass or less, more preferably 1.0% by mass or less, and even more preferably 0.8% by mass or less.

[0172] Mooney viscosity

[0173] The Mooney viscosity of the rubber-like polymer (A) used in the crosslinking rubber composition of this embodiment, the crosslinking agent (B) added later, and various additives is an indicator that includes information such as the molecular weight, molecular weight distribution, and degree of branching of the rubber-like polymer (A), as well as the content of softener, residual solvent, and water.

[0174] Regarding the Mooney viscosity of the rubber-like polymer (A) and the crosslinking rubber composition measured at 100°C, from the perspective of the abrasion resistance of the crosslinking rubber composition of this embodiment, the handling stability of the aforementioned tires after use in tire materials, and the breaking strength, it is preferably 40 or more, more preferably 50 or more, and even more preferably 55 or more. On the other hand, from the perspective of the productivity of the rubber-like polymer (A) and the crosslinking rubber composition, and the processability when preparing a rubber composition mixed with fillers, etc., it is preferably 170 or less, more preferably 150 or less, even more preferably 130 or less, and even more preferably 110 or less.

[0175] Mooney viscosity can be determined using the method specified in ISO 289, specifically, by the method described in the examples below.

[0176] Mooney stress relaxation rate

[0177] From the perspective of formability, the Mooney stress relaxation rate of the rubber-like polymer (A) used in the crosslinking rubber composition of this embodiment, the crosslinking rubber-like composition with the crosslinking agent (B) described later and various additives added, as measured at 100°C, is preferably 0.80 or less, more preferably 0.7 or less, and even more preferably 0.6 or less.

[0178] Mooney stress relaxation rate is an indicator of molecular entanglement in conjugated diene polymers. The lower the rate, the more molecular entanglement there is. The Mooney stress relaxation rate can be reduced by increasing the molecular weight of the rubbery polymer (A), increasing the degree of branching using the aforementioned coupling agents or branching agents, and reducing the amount of rubber softener added to increase the Mooney viscosity.

[0179] The Mooney stress relaxation rate can be determined as follows: A sample collected from a rubbery polymer (A) or a crosslinked rubber composition using a rubbery polymer (A) is preheated at 100°C for 1 minute, then a rotor is rotated at 2 rpm. The Mooney viscosity (ML) is determined based on the torque after 4 minutes. (1+4) Immediately after stopping the rotor, the torque was recorded every 0.1 seconds from 1.6 to 5 seconds after stopping, in Mooney units. A double logarithmic plot of torque versus time (seconds) was performed, and the slope of the straight line at this point was calculated. Its absolute value was taken as the Mooney stress relaxation rate.

[0180] (Rubber-like polymer (A), molding method of crosslinking rubber composition)

[0181] From a processability perspective, the rubber-like polymer (A) used in the crosslinking rubber composition of this embodiment, and the crosslinking rubber composition using this rubber-like polymer, are preferably molded into sheets or blocks. Blocks are more preferred, and 1,000 cm³ is even more preferred. 3 The above-mentioned block (pressed block) is further preferably a rectangular pressed block weighing 17.5kg to 35kg.

[0182] (Components of the crosslinking rubber composition)

[0183] The crosslinking rubber composition of this embodiment contains a crosslinking agent (B).

[0184] In addition, hydrogenated resin (C), other rubber components, filler oil, filler, and silane coupling agent may be included as needed.

[0185] (Cross-linking agent (B))

[0186] Examples of crosslinking agents (B) include sulfur-based crosslinking agents, organic peroxide-based crosslinking agents, inorganic crosslinking agents, polyamine crosslinking agents, resin crosslinking agents, sulfur-containing compound-based crosslinking agents, and oxime-nitrosoamine-based crosslinking agents. They can be used alone or in combination of two or more.

[0187] From the perspective of resistance to compression set and less degradation of physical properties over time, sulfur-based crosslinking agents (vulcanizing agents) are preferred, and sulfur is even more preferred.

[0188] It should be noted that the sulfur mentioned here refers to both powdered sulfur (soluble sulfur) and insoluble sulfur.

[0189] Regarding the content of the crosslinking agent (B) in the crosslinking rubber composition of this embodiment, from the perspective of tensile modulus, it is preferably 0.1 parts by mass or more and 20 parts by mass or less relative to 100 parts by mass of rubber component.

[0190] It should be noted that the above-mentioned "rubber components" include the rubber-like polymer (A) and other rubber components.

[0191] From the perspective of high tensile strength and high crosslinking speed, the content of crosslinking agent (B) is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 1.5 parts by mass or more, relative to 100 parts by mass of rubber component.

[0192] On the other hand, from the perspective of suppressing uneven crosslinking and high tensile strength, it is preferable to have 20 parts by mass or less, more preferably 5 parts by mass or less, and even more preferably 3 parts by mass or less.

[0193] When using a sulfur-based crosslinking agent (vulcanizing agent) as crosslinking agent (B), it is preferable to use a vulcanization accelerator in combination.

[0194] Especially when the iodine value of the rubbery polymer (A) is below 200 (g / 100g), it is preferable to use a vulcanization accelerator.

[0195] From the perspective of short crosslinking time and wear resistance of the rubber composition for crosslinking, the vulcanization accelerator is preferably, but not limited to, compounds such as guanidine, aldehyde-amine, aldehyde-amine, thiazole, sulfenamide, thiourea, thiuram, dithiocarbamate, and xanthate, and more preferably guanidine vulcanization accelerators such as 1,3-diphenylguanidine, thiazole vulcanization accelerators such as 2-mercaptobenzothiazole, dibenzothiazole disulfide, N-cyclohexylbenzothiazole-2-sulfenamide, and N-tert-butylbenzothiazole-2-sulfenamide.

[0196] A single vulcanization accelerator can be used alone, or two or more can be used in combination.

[0197] (Hydrogenated resin (C))

[0198] The crosslinking rubber composition of this embodiment may contain a hydrogenated resin (C).

[0199] By including the above-mentioned hydrogenated resin (C), the crosslinking rubber composition of this embodiment can suppress the reduction of processability, the reduction of tensile energy, and the reduction of abrasion resistance.

[0200] As the hydrogenated resin (C), a cyclic resin (C) is preferred, and a hydrogenated cyclic resin with a softening point of less than 140°C is more preferred.

[0201] In this specification, "resin containing rings (C)" means a resin having aromatic rings and / or aliphatic rings.

[0202] Generally, in tire rubber compositions, polymers having aromatic rings and / or aliphatic rings, being of low molecular weight, and in a glassy state at room temperature are mostly referred to as "resins" contained in the rubber composition. In this embodiment, the aforementioned resin is also preferably a hydrogenated resin (C).

[0203] Regarding the molecular weight of the hydrogenated resin (C), from the perspective of the high tensile energy of the crosslinking rubber composition of this embodiment, it is preferably 300 or more, and from the perspective of the processability of the crosslinking rubber composition, it is preferably 2500 or less.

[0204] From the perspective of the fracture resistance of the crosslinking rubber composition of this embodiment after it is made into a sheet, the glass transition temperature of the hydrogenated resin (C) is preferably 85°C or less, more preferably 80°C or less, and even more preferably 75°C or less. On the other hand, from the perspective of the rigidity of the crosslinking rubber composition of this embodiment and the operability of the crosslinking rubber composition during mixing, the temperature is preferably 25°C or more, more preferably 40°C or more, even more preferably 50°C, and even more preferably 110°C or more.

[0205] A rubbery polymer (A) with an iodine value of 10 to 250 (g / 100g) and an ethylene structure of ≥3% by mass, and a hydrogenated resin (C) with a softening point of less than 140°C, are easily mixed and have high compatibility. Therefore, by using the above-mentioned resin (C), there is a tendency to obtain good properties in the crosslinking rubber composition of this embodiment.

[0206] Regarding the softening point of the hydrogenated resin (C), from the perspective of the fracture resistance of the sheet using the crosslinking rubber composition of this embodiment, it is more preferably 135°C or lower, further preferably 130°C or lower, and even more preferably 125°C or lower. On the other hand, from the perspective of the rigidity of the crosslinking rubber composition of this embodiment and the operability of the crosslinking rubber composition during mixing, it is preferably 75°C or higher, more preferably 90°C or higher, further preferably 100°C, and even more preferably 110°C or higher.

[0207] Hydrogenated resin (C) is a resin formed by the partial or complete hydrogenation of unsaturated bonds within the molecule.

[0208] Specifically, it is a resin formed by partially or completely hydrogenating at least one unsaturated group selected from the group consisting of aromatic rings such as benzene rings, cyclopentadiene, dicyclopentadiene, and terpene structures.

[0209] As a hydrogenation method, examples include a method for hydrogenating a resin having intramolecular unsaturated bonds under hydrogen pressure of 1 to 100 atmospheres by using at least one of the following substances as a hydrogenation catalyst: nickel organic carboxylate, cobalt organic carboxylate, or a hydrogenation catalyst composed of organometallic compounds of groups 1 to 3; a metal catalyst consisting of nickel, platinum, palladium, ruthenium, or rhodium supported on carbon, silicon oxide, or diatomaceous earth; or a complex of cobalt, nickel, rhodium, or ruthenium.

[0210] The resin before hydrogenation can be either a natural resin or a synthetic resin.

[0211] Commercially available products can be used as the aforementioned hydrogenated resin (C). Examples of such commercially available products include, but are not limited to, those manufactured by Idemitsu Kosan Co., Ltd., which uses C5 fraction as the main raw material and is a DCPD (dicyclopentadiene) / aromatic (C9) copolymer hydrogenated petroleum resin under the trade names "I-Marv P100", "I-Marv P125", "I-Marv S100", and "I-Marv S110" as a hydrogenated petroleum resin; and those manufactured by Arakawa Chemical Industry Co., Ltd., which uses C9 fraction as the main raw material and is a hydrogenated resin under the trade names "Arkon P-90", "Arkon P-100", "Arkon P-115", "Arkon P-125", "Arkon M-90", "Arkon M-100", and "Arkon M-115" as a hydrogenated resin. M-135 (P for fully hydrogenated, M for partially hydrogenated); T-REZ OP501, T-REZ PR801, T-REZ HA125, and T-REZ HB125, manufactured by Tonen General Petroleum Co., Ltd., as DCPD (dicyclopentadiene) / aromatic (C9) copolymer hydrogenated petroleum resins; and Cleanon P105, Cleanon P115, Cleanon P125, Cleanon P135, Cleanon P150 (trade name, softening point 152°C), Cleanon M105, and Cleanon... all manufactured by YASUHARA CHEMICAL, as terpene-based hydrogenated resins. M115, Cleanon K100 manufactured by YASUHARA CHEMICAL, Cleanon K110 manufactured by YASUHARA CHEMICAL, Cleanon K4100 manufactured by YASUHARA CHEMICAL, Cleanon K4090 manufactured by YASUHARA CHEMICAL, etc.

[0212] These hydrogenated resins (C) can be used alone or in combination of two or more.

[0213] (Other rubber components)

[0214] In addition to the rubber polymer (A) described above, the crosslinking rubber composition of this embodiment may also contain other rubber components.

[0215] Other rubber components can be selected appropriately according to the purpose, and examples include, but are not limited to, styrene-butadiene rubber (emulsion polymerization type or solution polymerization type), natural rubber, polyisoprene, butadiene rubber (high cis polybutadiene, low cis polybutadiene, syndiotactic 1,2-polybutadiene, nitrile rubber (NBR)), chloroprene rubber, ethylene-propylene rubber, ethylene-butene rubber, ethylene-octene and other ethylene-α-olefin copolymer rubbers, ethylene-propylene-diene rubber (EPDM), butyl rubber, polysulfide rubber, silicone rubber, fluororubber and urethane rubber, etc.

[0216] These ingredients can be used alone or in combination of two or more.

[0217] Other rubber components can be mixed in a dry state after the polymerization of the rubber polymer (A), or they can be mixed in a solution state during the polymerization of the rubber polymer (A).

[0218] (The content of rubbery polymer (A) in the total rubber composition)

[0219] From the perspectives of mechanical strength, fuel efficiency when used in tire components, ozone resistance, and storage stability, in the crosslinking rubber composition of this embodiment, the content of rubber-like polymer (A) relative to the total amount of rubber component is preferably 10% by mass or more, more preferably 30% by mass or more, and even more preferably 60% by mass or more. That is, the crosslinking rubber composition of this embodiment contains 100 parts by mass of rubber component, which preferably contains 10 parts by mass or more, more preferably 30 parts by mass or more, and even more preferably 60 parts by mass or more of rubber-like polymer (A).

[0220] Especially in applications such as tire rubber compositions, tire sidewalls, tire bead wraps, and tire steel belt coated rubber, as described later, it is preferable that the content of the rubbery polymer (A) is 30% by mass or more relative to the total amount of rubber components.

[0221] (Average iodine value of total rubber components)

[0222] From the perspective of suppressing uneven crosslinking and obtaining high mechanical strength, the average iodine value of the total amount of rubber components in the crosslinking rubber composition of this embodiment is preferably 250 (g / 100g) or less, more preferably 200 (g / 100g) or less, further preferably 130 (g / 100g) or less, and even more preferably 70 (g / 100g) or less.

[0223] (Other components of the crosslinking rubber composition)

[0224] <Filling Oil>

[0225] In the crosslinking rubber composition of this embodiment, from the perspective of ensuring good moldability after mixing, it is preferable to contain filler oil.

[0226] In this embodiment, the content of filler oil in the crosslinking rubber composition is preferably 1 part by mass or more, and more preferably 3 parts by mass or more, relative to 100 parts by mass of the total rubber components. By making the content of filler oil 1 part by mass or more, the processability of the mixture is improved.

[0227] On the other hand, the content of the filler oil relative to 100 parts by weight of the rubber component is preferably 50 parts by weight or less, more preferably 30 parts by weight or less, even more preferably 10 parts by weight or less, and even more preferably 5 parts by weight or less. By making the content of the filler oil 50 parts by weight or less, there is a tendency to further improve the abrasion resistance of the crosslinking rubber composition.

[0228] As filler oils, aromatic oils, cycloalkanes, and paraffins are preferred. Among these, from the perspectives of environmental safety, prevention of oil seepage, and wetland grip properties, alternative aromatic oils with a polycyclic aromatic (PCA) content of 3% by mass or less based on the IP346 standard are preferred.

[0229] As alternative aromatic oils, examples include, but are not limited to, TDAE (Treated Distillate Aromatic Extracts), MES (Mild Extraction Solvate), and RAE (Residual Aromatic Extracts), as shown in Kautschuk Gummi Kunststoffe 52(12)799(1999).

[0230] Vegetable oils can be used as filler oils. Compared to using synthetic or mineral oils, using vegetable oils as filler oils improves the moldability of the compounded mixture while protecting the environment.

[0231] Examples of vegetable oils include, but are not limited to, flaxseed oil, safflower oil, soybean oil, corn oil, cottonseed oil, turnip seed oil, castor oil, tung oil, pine oil, sunflower seed oil, palm oil, olive oil, coconut oil, peanut oil, and grapeseed oil, with sunflower seed oil being particularly preferred. These vegetable oils can be used individually or in combination of two or more.

[0232] <filler>

[0233] In the crosslinking rubber composition of this embodiment, a filler can be used from the perspective of improving reinforcement.

[0234] The filler content in the crosslinking rubber composition of this embodiment can be suitably selected according to the purpose. From the perspective of reinforcement, it is preferably greater than 30 parts by weight, more preferably greater than 50 parts by weight, further preferably greater than 60 parts by weight, and even more preferably greater than 70 parts by weight relative to 100 parts by weight of rubber component. On the other hand, from the perspective of processability of crosslinking rubber composition, it is preferably 130 parts by weight or less, more preferably 120 parts by weight or less.

[0235] Examples of fillers include, but are not limited to, carbon black, silicon dioxide, aluminum hydroxide, clay, alumina, talc, mica, kaolin, hollow glass spheres, glass beads, calcium carbonate, magnesium carbonate, magnesium hydroxide, magnesium oxide, titanium dioxide, potassium titanate, and barium sulfate, among which carbon black is preferred.

[0236] These substances can be used alone or in combination of two or more.

[0237] As carbon black, appropriate types can be selected according to the purpose, such as SRF, GPF, FEF, HAF, ISAF, SAF, etc. They can be used alone or in combination of two or more.

[0238] In addition, the nitrogen adsorption specific surface area (N2SA, determined according to JIS K6217-2:2001) of the above-mentioned carbon black can be appropriately selected according to the purpose.

[0239] Of the fillers described above, carbon black is preferred from the perspective of improving the reinforcing properties of the crosslinking rubber composition of this embodiment, and carbon black is preferred to be used in combination with silicon oxide from the perspective of improving fuel efficiency after the crosslinking rubber composition is used in tire parts.

[0240] Furthermore, when using silica as a filler, from the perspective of balancing improved fuel efficiency and tensile strength, the silica content in the crosslinking rubber composition of this embodiment is preferably 10 to 50 parts by mass relative to 100 parts by mass of the rubber component, more preferably 20 to 40 parts by mass, and even more preferably 25 to 35 parts by mass.

[0241] In this embodiment, the nitrogen adsorption specific surface area (BET specific surface area) of the carbon black used in the crosslinking rubber composition is preferably 20 m². 2 / g or more, preferably 30m 2 / g or more, further preferably 40m 2 / g or more, further preferably 50m 2 / g or more.

[0242] By making the nitrogen adsorption specific surface area of ​​carbon black 20m² 2Achieving a nitrogen adsorption surface area of ​​30 m² or higher yields excellent reinforcing effects, resulting in superior rubber breaking strength and handling stability. 2 A weight of 1 g or more can achieve sufficient reinforcement, resulting in adequate rubber breaking strength and handling stability.

[0243] The preferred nitrogen adsorption specific surface area (BET specific surface area) of carbon black is 150 m². 2 / g or less, more preferably 130m 2 / g or less, more preferably 120m 2 / g or less. By making the nitrogen adsorption specific surface area 150m². 2 Good low fuel consumption can be achieved when the concentration is below / g.

[0244] In this embodiment, the nitrogen adsorption specific surface area (BET specific surface area) of the silica-based inorganic filler used in the crosslinking rubber composition is preferably 110 m². 2 / g or more, preferably 130m 2 / g or more, further preferably 150m 2 / g or more.

[0245] By making the nitrogen adsorption specific surface area of ​​the silica-based inorganic filler 110 m² 2 A nitrogen adsorption specific surface area (BET specific surface area) of 220 m² or higher can achieve sufficient reinforcing effect, resulting in adequate rubber breaking strength and handling stability. 2 / g or less, more preferably 200m 2 / g or less, more preferably 180m 2 / g or less. By making it 220m 2 Good low fuel consumption can be achieved when the concentration is below / g.

[0246] There are no particular limitations on the use of silica-based inorganic fillers. For example, solid particles containing SiO2 or Si3Al as structural units are preferred, and solid particles containing SiO2 or Si3Al as the main structural unit are more preferred.

[0247] Here, the main component refers to the component that contains 50% or more by mass, preferably 70% or more by mass, and more preferably 80% or more by mass in the silica-based inorganic filler.

[0248] Examples of silica-based inorganic fillers include, but are not limited to, inorganic fibrous materials such as silica, clay, talc, mica, diatomaceous earth, wollastonite, montmorillonite, zeolite, and glass fiber.

[0249] Commercially available products that serve as silica-based inorganic fillers include, for example, the product manufactured by Evonik Degussa under the trade name "Ultrasil 7000GR".

[0250] In addition, as a silica-based inorganic filler, a silica-based inorganic filler with a hydrophobic surface, or a mixture of a silica-based inorganic filler and an inorganic filler other than silica-based fillers can also be used.

[0251] Among these, silica and glass fiber are preferred in terms of strength and wear resistance, with silica being more preferred. Examples of silica include dry silica, wet silica, and synthetic silicate silica. Among these, wet silica is further preferred in terms of its superior balance between improved destructive properties and excellent anti-slip properties.

[0252] In addition, the nitrogen adsorption specific surface area (N2SA) mentioned above can be determined according to JIS K6217-2:2001.

[0253] <Silane coupling agent>

[0254] In the crosslinking rubber composition of this embodiment, from the perspective of improving the dispersibility of fillers and the tensile strength of crosslinked bodies, a silane coupling agent is preferably included.

[0255] Silane coupling agents have the function of making the interaction between rubber components and inorganic fillers more intense. They have groups that have affinity or binding with the rubber components and fillers, respectively, and are preferably compounds that have a sulfur-binding moiety and an alkoxysilyl or silanol moiety in one molecule.

[0256] Examples of such compounds include, but are not limited to, bis-[3-(triethoxysilyl)-propyl]-tetrasulfide, bis-[3-(triethoxysilyl)-propyl]-disulfide, bis-[2-(triethoxysilyl)-ethyl]-tetrasulfide, 3-octanoylthiopropyltriethoxysilane, condensates of 3-octanoylthiopropyltriethoxysilane with [(triethoxysilyl)-propyl]thiol, and silanes supported with at least one thiol (-SH) functional group (referred to as mercaptosilane) and / or at least one masked mercapto group.

[0257] The content of the silane coupling agent in the crosslinking rubber composition of this embodiment is preferably 0.1 parts by mass or more and 30 parts by mass or less, more preferably 0.5 parts by mass or more and 20 parts by mass or less, and even more preferably 1.0 parts by mass or more and 10 parts by mass or less, relative to 100 parts by mass of the filler. When the content of the silane coupling agent is within the above range, it tends to make the above-mentioned additive effect brought about by the silane coupling agent more significant.

[0258] <Other Additives>

[0259] In addition to the various components described above, the crosslinking rubber composition of this embodiment may also use various additives such as softeners, fillers, heat stabilizers, antistatic agents, weather stabilizers, anti-aging agents, colorants, and lubricants.

[0260] Other known plasticizers can be used as alternatives.

[0261] Other fillers that can be cited include calcium carbonate, magnesium carbonate, aluminum sulfate, and barium sulfate.

[0262] The aforementioned heat stabilizers, antistatic agents, weather stabilizers, anti-aging agents, colorants, and lubricants can each be made from known materials.

[0263] [Method for manufacturing crosslinking rubber composition]

[0264] The crosslinking rubber composition of this embodiment is obtained by mixing a rubber-like polymer (A), a crosslinking agent (B), and, if necessary, a hydrogenated resin (C), other rubber components, filler oil, silica-based inorganic filler, carbon black or other filler, silane coupling agent, rubber softener, and other additives.

[0265] Regarding mixing methods, examples include, but are not limited to, melt mixing using common mixers such as open mills, Banbury mixers, kneaders, single-screw extruders, twin-screw extruders, and multi-screw extruders, as well as methods that involve dissolving and mixing the components and then heating to remove the solvent.

[0266] Among these methods, the melt mixing method using rollers, Banbury mixers, kneaders, and extruders is preferred in terms of productivity and good mixing properties.

[0267] Alternatively, it can be applied to either a method of mixing the rubber component with other fillers, silane coupling agents, and additives in one step, or a method of mixing in multiple steps.

[0268] [Rubber Composition for Tires]

[0269] The tire rubber composition of this embodiment contains 100 parts by weight of a rubber component and the crosslinking agent (B) described above. The rubber component includes 30 parts by weight or more of natural rubber and 10 parts by weight or more of the rubbery polymer (A) described above.

[0270] The content of the rubber-like polymer (A) is preferably 30 parts by mass or more, more preferably 60 parts by mass or more, in 100 parts by mass of the rubber component.

[0271] This results in good processability during mixing, leading to a tire rubber composition with excellent balance of physical properties.

[0272] Examples of applications for the tire rubber composition of this embodiment include tire components such as tire sidewalls, rubber bead wraps, steel belt coatings, and bead filler. The tire rubber composition of this embodiment can be suitably molded according to its application. For example, it can be molded into a sheet or integrally molded as a covered cord or belt.

[0273] The tire rubber composition of this embodiment preferably further contains a nitrogen adsorption specific surface area (N2SA) of 20 to 150 m². 2 The specific surface area (N2SA) of carbon black and / or nitrogen adsorption per gram is 110–220 m². 2 / g of silica-based inorganic filler.

[0274] This results in a tire rubber composition with excellent fuel efficiency, tensile strength, and resistance to ozone degradation (ozone resistance).

[0275] The nitrogen adsorption specific surface area (N2SA) is 20–150 m². 2 The specific surface area (N2SA) of carbon black and / or nitrogen adsorption per gram is 110–220 m². 2 The content of silica-based inorganic filler per g, from the perspective of balancing processability and physical properties, is preferably 30 parts by mass or more, more preferably 40 parts by mass or more, and even more preferably 50 parts by mass or more, relative to the aforementioned 100 parts by mass of rubber component containing 30 parts by mass or more of natural rubber and 10 parts by mass or more of rubbery polymer (A). Regarding the upper limit of the content of carbon black and / or silica-based inorganic filler, it is preferably 90 parts by mass or less, more preferably 80 parts by mass or less, and even more preferably 70 parts by mass or less.

[0276] It should be noted that, when the content of the rubber-like polymer (A) in 100 parts by mass of the rubber component is 10 parts by mass or more as described above, although it may contain 30 parts by mass or more of carbon black and / or silica-based inorganic fillers, since the rubber-like polymer (A) has modifying groups and high affinity with hydrophilic carbon black and / or silica-based inorganic fillers, from the perspective of the dispersibility of the aforementioned carbon black and / or silica-based inorganic fillers, it is preferable to have a higher content of rubber-like polymer (A) or a higher modification rate of rubber-like polymer (A). In the rubber composition containing carbon black and / or silica-based inorganic fillers, when increasing the content of rubber-like polymer (A) to improve the dispersibility of the filler, the content of rubber-like polymer (A) in 100 parts by mass of the rubber component is preferably 30 parts by mass or more. In this composition, the upper limit of the content of carbon black and / or silica-based inorganic filler depends on the functional groups contained in the rubbery polymer (A) and the modification rate, but is preferably 100 parts by mass or less, more preferably 90 parts by mass or less.

[0277] [Molded components for tire sidewalls]

[0278] The tire sidewall molding body of this embodiment contains the crosslinking rubber composition of this embodiment described above. It is a molding body of the following composition, which contains 100 parts by mass of a rubber component comprising at least 30 parts by mass of natural rubber and at least 10 parts by mass of the aforementioned rubbery polymer (A); and a nitrogen adsorption specific surface area (N2SA) of 20 to 150 m². 2 The specific surface area (N2SA) of carbon black and / or nitrogen adsorption per gram is 110–220 m². 2 / g of silica-based inorganic filler 30-70 parts by weight, further containing the above-mentioned crosslinking agent (B).

[0279] The tire sidewall molding body of this embodiment is typically a sheet-like molding body. It is overlapped with sheet-like molding bodies used to form other parts besides the tire sidewall, molded into the shape of a tire, and then cross-linked. The composition ratio of the rubber component in the sidewall molding body can be appropriately set according to the desired sidewall performance. For example, to improve the dispersibility and ozone resistance of the silica-based inorganic filler, it is preferable to set the composition of the rubber component in 100 parts by mass such that it contains at least 30 parts by mass of natural rubber and at least 10 parts by mass of the aforementioned rubbery polymer (A).

[0280] For the performance requirements of the molded body used in tire sidewalls, fuel efficiency, tensile strength, and resistance to ozone degradation (ozone resistance) are particularly important.

[0281] As mentioned above, since the rubbery polymer (A) is a polymer with a certain iodine value (10-250 g / 100g), by blending it, the crosslinked body forms a uniform structure, improving tensile strength. Furthermore, due to the fewer double bonds, it is less susceptible to ozone attack, resulting in good ozone resistance. It should be noted that regarding fuel efficiency, it is speculated that in the exothermic property index of rubber tanδ = G'' / G' = loss modulus / storage modulus, by blending the aforementioned rubbery polymer (A), although the value of G' is high, G'' is not actually that high. Therefore, the result is a low tanδ value, i.e., low exothermic property and excellent fuel efficiency.

[0282] It should be noted that it is speculated that the high value of the storage modulus G' is due to the decrease in molecular weight between entanglement points caused by the hydrogenation of the rubbery polymer (A), which increases the entanglement between polymers.

[0283] In addition, when the crosslinking rubber composition of this embodiment contains natural rubber, it is preferred from the perspective of balancing tensile strength and low exothermicity as well as processability, but on the other hand, the weather resistance tends to deteriorate.

[0284] Furthermore, conjugated diene polymers such as butadiene rubber exhibit excellent flexural strength and low exothermic properties, making them suitable for use in tire sidewalls. However, their breaking strength is inferior to that of natural rubber. Therefore, to balance the full range of properties including flexural strength, low exothermic properties, and breaking strength, it is preferable to combine butadiene rubber with natural rubber.

[0285] By using a natural rubber / rubber-like polymer (A) ratio of 30 / 70 to 70 / 30, various physical properties, including weather resistance, are found to be practically sufficient in the molded body for tire sidewalls, and the content and properties can be controlled according to the application. The ratio of natural rubber to rubber-like polymer (A) can also be appropriately changed according to their respective costs, etc.

[0286] In the rubber composition constituting the tire sidewall molding body of this embodiment, by setting the content of natural rubber to 30 parts by mass or more relative to the total amount of rubber components, it tends to have good processability during mixing and can improve the balance of physical properties.

[0287] [Sheet]

[0288] The sheet of this embodiment contains the crosslinking rubber composition of this embodiment described above.

[0289] The sheet material of this embodiment preferably contains a rubber component, wherein 100 parts by weight of the rubber component includes 30 parts by weight or more of natural rubber, 10 parts by weight or more of butadiene rubber, and 10 parts by weight or more of the above-mentioned rubbery polymer (A).

[0290] From the perspective of fuel efficiency, the content of rubber-like polymer (A) in 100 parts by mass of rubber component is more preferably 20 parts by mass or more, and even more preferably 30 parts by mass or more.

[0291] Furthermore, the rubbery polymer (A) contained in the sheet of this embodiment preferably has a glass transition temperature of -60°C or less and a weight-average molecular weight of 200,000 or more.

[0292] With the above-described structure, the sheet of this embodiment has high mechanical strength, high fuel efficiency, and high ozone resistance.

[0293] As an example of the application of the sheet material in this embodiment, it can be used to manufacture tire components such as tire sidewalls. The mixing ratio of rubber components, the type and amount of fillers and additives can be appropriately adjusted according to the required function of the component using the sheet material of this embodiment.

[0294] The width and thickness of the sheet material in this embodiment can be appropriately adjusted according to the size of the component being applied or the final tire size. The thickness is typically around 0.5 to 3 cm. The width is approximately 0.5 to 1.0 times the tire size; for example, for passenger car applications, although it depends on the tire shape, a sheet size of approximately 15 to 300 mm is preferred.

[0295] The sheet material in this embodiment preferably further contains a nitrogen adsorption specific surface area (N2SA) of 20 to 150 m². 2 The specific surface area (N2SA) of carbon black and / or nitrogen adsorption per gram is 110–220 m². 2 / g of silica-based inorganic filler.

[0296] The nitrogen adsorption specific surface area (N2SA) is 20–150 m². 2 The specific surface area (N2SA) of carbon black and / or nitrogen adsorption per gram is 110–220 m². 2 The content of the silica-based inorganic filler per g is preferably 50 to 90 parts by mass, more preferably 50 to 85 parts by mass, and even more preferably 50 to 80 parts by mass, relative to the 100 parts by mass of the rubber component containing 30 or more parts by mass of natural rubber, 10 or more parts by mass of butadiene rubber, and 10 or more parts by mass of rubbery polymer (A).

[0297] This results in sheets that are fuel-efficient and have excellent tensile strength.

[0298] In the sheet manufacturing process of this embodiment, it is very important that the rubber-like polymer (A) is well compatible with natural rubber and butadiene rubber when they are mixed.

[0299] In common tire manufacturing processes, raw materials constituting a rubber composition are mixed, formed into sheets, and then tended to be stored for a certain period before vulcanization. When the rubbers have poor compatibility, this storage can lead to changes in the tensile properties and other physical properties of the vulcanized molded body. This is believed to be because phase separation or changes in phase structure or filler dispersion occur within the rubber composition during storage, resulting in stress concentration points within the vulcanized molded body. In other words, if a manufacturing process is based on storing the molded sheets for a certain period before vulcanization to achieve crosslinking, then ensuring sufficient compatibility of the rubbers constituting the rubber composition is crucial for the tire components to exhibit the desired performance.

[0300] From this perspective, the rubbery polymer (A) is preferably well-compatible with both natural rubber and butadiene rubber. Specifically, the glass transition temperature of the rubbery polymer (A) is preferably below -60°C. Therefore, it generally exhibits excellent compatibility with both natural rubber (with a glass transition temperature of -50°C to -70°C) and butadiene rubber (with a glass transition temperature of -110°C to -90°C), and the rubber composition tends to have excellent long-term stability during storage.

[0301] In addition, the compatibility of the rubbery polymer (A) with natural rubber and butadiene rubber is related to the SP value and glass transition temperature Tg of the rubbery polymer (A).

[0302] The SP value and glass transition temperature Tg of the rubbery polymer (A) can be controlled by adjusting the 1,2-vinyl binding amount, the amount of vinyl aromatic monomer units, and the hydrogenation rate of the rubbery polymer (A).

[0303] In a specific three-component system of natural rubber, butadiene rubber and rubber-like polymer (A), the relationship between the SP value and Tg that the rubber-like polymer (A) should satisfy was experimentally determined from the perspective of good compatibility. It was found that by making the SP value and the glass transition temperature Tg satisfy the following formula (1), it tends to be compatible with both natural rubber and butadiene rubber.

[0304] Equation (1): (-0.03Tg+14.4) < SP value < (-0.03Tg+15.4) In the above formula (1), the SP value of the rubbery polymer (A) is given by formula (SP value) = ((molar cohesive energy) / (molar volume)). 1 / 2 Calculated.

[0305] When a rubbery polymer (A) is composed of two or more different components, the additivity of molar cohesive energy holds. Therefore, the molar cohesive energy of the rubbery polymer (A) is calculated as the average of the molar cohesive energies based on the content (mol%) of each component (an average distributed proportionally according to their content). Similarly, the additivity of molar volumes also holds, and the molar volume of the rubbery polymer (A) is calculated as the average of the molar volumes based on the content (mol%) of each component (an average distributed proportionally according to their content).

[0306] The above two or more different components are not particularly limited. Examples include conjugated diene monomer units and vinyl aromatic monomer units embedded in various ways such as unhydrogenated 1,2-linked, hydrogenated 1,2-linked, unhydrogenated 3,4-linked, hydrogenated 3,4-linked, unhydrogenated 1,4-linked, and hydrogenated 1,4-linked.

[0307] It should be noted that the amounts of conjugated diene monomer units and vinyl aromatic monomer units embedded in each bonding mode can be determined by NMR or other methods.

[0308] It should be noted that the molar volume and molar cohesive energy of the conjugated diene monomer units, vinyl aromatic monomer units, and other monomer units embedded in various bonding modes of unhydrogenated 1,2-bonded, hydrogenated 1,2-bonded, unhydrogenated 3,4-bonded, hydrogenated 3,4-bonded, unhydrogenated 1,4-bonded, and hydrogenated 1,4-bonded can be determined using the method described in J. Bicerano, Prediction of Polymer Properties, 3rd Ed. Marcel Dekker, 2002 (Bicerano method).

[0309] By controlling the 1,2-vinyl binding amount of the conjugated diene monomer unit, the content of the vinyl aromatic monomer unit, and the hydrogenation rate, the SP value of the rubber-like polymer (A) can be controlled within the numerical range satisfying the above formula (1). For example, if the rubber-like polymer (A) is a hydrogenated copolymer of styrene and butadiene, the SP value of the rubber-like polymer (A) can be reduced by decreasing the styrene content and / or increasing the 1,2-vinyl binding amount of the butadiene monomer unit and / or increasing the hydrogenation rate. As for the fluctuation range of the SP value when changing each structural factor, although it also depends on its structure, for example, when the other two are fixed and only the styrene content is reduced by 10% by mass, the SP value decreases by about 0.20 to 0.25; when only the 1,2-vinyl binding amount of the butadiene monomer unit is increased by 10 mol%, the SP value decreases by about 0.025 to 0.050; and when the hydrogenation rate is increased by 10 mol%, the SP value decreases by about 0.05 to 0.10. Conversely, by increasing the amount of styrene and / or decreasing the 1,2-vinyl binding of butadiene monomer units and / or decreasing the hydrogenation rate, the SP value can be increased by the same amount of variation.

[0310] In the rubber-like polymer (A), if the 1,2-vinyl binding amount of the conjugated diene monomer unit, the content of the vinyl aromatic monomer unit, and the hydrogenation rate are controlled, the glass transition temperature Tg will also change in addition to the SP value. In order to satisfy the above formula (1), for example, in the case that the rubber-like polymer (A) is a hydrogenated copolymer of styrene and butadiene, it is preferable to make the styrene content 20% by mass or less. If the styrene content is increased, in order to satisfy the above formula (1), the 1,2-vinyl content needs to be reduced as the structure of the rubber-like polymer (A). If the styrene content is greater than 20% by mass, it tends to be difficult to control the structure of the rubber-like polymer (A) in a manner that satisfies the above formula (1).

[0311] In the sheet of this embodiment, when RSS#3 is used as natural rubber and high cis polybutadiene is used as butadiene rubber as a specific rubber component, the structure of a rubber-like polymer (A) having physical properties in a range similar to the Tg and SP values ​​of each rubber component can be defined by the above formula (1).

[0312] Specifically, when the Tg and SP values ​​of natural rubber and butadiene rubber are set as follows: natural rubber (RSS): Tg = -62℃, SP value: 16.7; butadiene rubber (high cis polybutadiene): Tg = -95℃, SP value: 17.7, the coefficient -0.03 in equation (1) corresponds to the slope when drawing a straight line connecting the two. Furthermore, regarding the intercept in equation (1), by falling within the range specified in equation (1), the characteristics of both natural rubber (RSS#3) and butadiene rubber (high cis polybutadiene) can be included.

[0313] By making the Tg and SP values ​​of the rubbery polymer (A) satisfy the above formula (1), the properties of natural rubber and butadiene rubber are similar, and the compatibility is better.

[0314] Since natural rubber is mostly composed of 1,4-cis-polyisoprene, there is no significant difference in the Tg and SP values ​​of commonly available natural rubber. Therefore, regardless of which type of natural rubber is selected, it tends to show good compatibility with the rubber-like polymer (A) that satisfies the above formula (1).

[0315] On the other hand, depending on the bonding mode of butadiene (cis-type, trans-type), the Tg and SP values ​​of polybutadiene differ, and low-cis polybutadiene with a low 1,4-cis content is also commercially available. The Tg and SP values ​​of polybutadiene also depend on the structure, but in the case of polybutadiene with a low cis content, such as about 15 mol% of 1,2-vinyl bonding, the Tg is -90°C and the SP value is about 17.6, showing good compatibility with the rubbery polymer (A) that satisfies the above formula (1).

[0316] In the sheet of this embodiment, the content of the rubber-like polymer (A) is preferably 10 parts by mass or more, more preferably 20 parts by mass or more, and even more preferably 30 parts by mass or more, relative to 100 parts by mass of the rubber component containing the rubber-like polymer (A). By making the content of the rubber-like polymer (A) 10 parts by mass or more, there is a tendency to obtain a sheet with excellent fuel efficiency.

[0317] The content of the rubber-like polymer (A) relative to 100 parts by weight of the rubber component is preferably 60 parts by weight or less, more preferably 55 parts by weight or less, and even more preferably 50 parts by weight or less. By keeping the content of the rubber-like polymer (A) at 60 parts by weight or less relative to 100 parts by weight of the rubber component, there is a tendency to obtain sheets with excellent mechanical strength by increasing the proportion of natural rubber in the blend.

[0318] The sheet material of this embodiment may also contain other components besides the crosslinking rubber composition of this embodiment. The proportions of the components and additives can be appropriately set according to the application, and more specifically, set to the preferred ranges for each application described below.

[0319] [Tire sidewall]

[0320] The sheet of the above-described present embodiment can be used for a tire sidewall.

[0321] The tire sidewall of the present embodiment contains: 10 parts by mass or more of a rubbery polymer (A) having an iodine value of 10 to 250 (g / 100g), an ethylene structure content of ≧3 mass%, a vinyl aromatic monomer block content of <10 mass%, containing nitrogen atoms, a modification rate of 40 mass% or more as measured by column adsorption GPC method, a glass transition temperature of -60°C or lower, and a weight average molecular weight of 200,000 or more; 30 parts by mass or more of natural rubber; and 10 parts by mass or more of butadiene rubber, and has a structure in which the rubbery polymer (A), the natural rubber and the butadiene rubber are crosslinked.

[0322] With the above configuration, a tire sidewall having high mechanical strength, high fuel efficiency, and high ozone resistance can be obtained.

[0323] In the tire sidewall of the present embodiment, the SP value and the glass transition temperature Tg of the rubbery polymer (A) preferably satisfy the following formula (1).

[0324] Formula (1): (-0.03×Tg+14.4)<SP value<(-0.03×Tg+15.4) By satisfying the above formula (1), when the tire sidewall of the present embodiment contains a rubber component including the rubbery polymer, natural rubber and butadiene rubber, the rubbery polymer (A) has excellent compatibility with natural rubber and butadiene rubber, and a tire sidewall with excellent storage stability can be obtained.

[0325] The tire sidewall of the present embodiment preferably contains carbon black having a nitrogen adsorption specific surface area (N2SA) of 20 to 150 m 2 / g and / or a silica-based inorganic filler having a nitrogen adsorption specific surface area (N2SA) of 110 to 220 m 2 / g.

[0326] Further, in the tire sidewall of the present embodiment, relative to 100 parts by mass of the rubber component comprising 10 parts by mass or more of the rubbery polymer (A), 30 parts by mass or more of natural rubber and 10 parts by mass or more of butadiene rubber, the tire sidewall preferably contains 50 to 90 parts by mass of the above carbon black and / or silica-based inorganic filler, and the above crosslinking agent (B).

[0327] Thereby, a sheet excellent in fuel efficiency and tensile strength can be obtained.

[0328] (Method for manufacturing tire sidewall)

[0329] The tire sidewall manufacturing method of this embodiment includes the following steps: mixing the crosslinking rubber composition of this embodiment, natural rubber, and butadiene rubber to obtain a sheet-like molded body, and crosslinking the sheet-like molded body. It should be noted that in the sheet-like molded body, 100 parts by mass of the rubber component includes at least 30 parts by mass of the natural rubber, at least 10 parts by mass of the butadiene rubber, and at least 10 parts by mass of the rubber-like polymer (A).

[0330] [Tire bead wrapping]

[0331] When the sheet of this embodiment is used for the rubber bead covering of a tire, the sheet of this embodiment preferably contains: 100 parts by mass of a rubber component comprising at least 40 parts by mass of natural rubber and at least 30 parts by mass of the aforementioned rubbery polymer (A); and a nitrogen adsorption specific surface area (N2SA) of 20 to 150 m². 2 The specific surface area (N2SA) of carbon black and / or nitrogen adsorption per gram is 110–220 m². 2 50-90 parts by weight of silica-based inorganic filler per g, further containing the above-mentioned crosslinking agent (B).

[0332] The performance requirements and compounding conditions for the rubber bead wrapping of the tire are the same as those for the tire sidewalls mentioned above, but special emphasis is placed on fuel efficiency and tensile strength. In particular, due to the characteristics of the components, a high tensile strength of no less than that of the tire sidewalls mentioned above is required.

[0333] As described above, since the rubber-like polymer (A) is a polymer with a certain iodine value (10-250 g / 100g), the crosslinked body forms a uniform structure, resulting in increased tensile strength. The rubber bead wrapping of tires has a higher proportion of filler than the tire sidewall in terms of component characteristics. To ensure good compounding processability, there is a tendency to require a higher proportion of natural rubber than in the tire sidewall. From this perspective, by ensuring a natural rubber content of 40 parts by mass or more relative to 100 parts by mass of the total rubber component, good processability during compounding can be ensured, and there is a tendency to achieve a good balance of physical properties.

[0334] [The steel belt coating rubber of the tire]

[0335] When the sheet of this embodiment is used in the steel belt coating rubber of a tire, the sheet of this embodiment preferably contains: 100 parts by mass of a rubber component comprising at least 30 parts by mass of natural rubber and at least 30 parts by mass of the aforementioned rubbery polymer (A); and a nitrogen adsorption specific surface area (N2SA) of 20 to 150 m². 2 The specific surface area (N2SA) of carbon black and / or nitrogen adsorption per gram is 110–220 m². 2The product contains 40-80 parts by weight of silica-based inorganic filler per gram, and further contains a crosslinking agent (B).

[0336] The performance requirements and compounding conditions for the steel belt coated rubber of tires are the same as those for the tire sidewalls, but greater emphasis is placed on fuel efficiency and tensile strength. Due to the characteristics of the components, the steel belt coated rubber of tires requires a tensile strength no lower than that of the tire sidewalls, and also requires low heat release (fuel efficiency).

[0337] As described above, since the rubber-like polymer (A) is a polymer with a certain iodine value (10-250 (g / 100g)), the crosslinked body forms a uniform structure, and the tensile strength can be expected to be improved.

[0338] In addition, as another characteristic, the steel belt coating rubber of the tire requires excellent adhesion. Therefore, it is necessary to contain natural rubber with excellent adhesion to metal. By blending at least 30 parts by mass of natural rubber relative to 100 parts by mass of the total rubber component, there is a tendency for excellent adhesion to metal and a good balance of physical properties.

[0339] [Tire bead filler]

[0340] When the sheet of this embodiment is used as a bead filler in a tire, the sheet of this embodiment preferably contains: 100 parts by mass of a rubber component comprising at least 40 parts by mass of natural rubber and at least 30 parts by mass of the aforementioned rubbery polymer (A); and a nitrogen adsorption specific surface area (N2SA) of 20 to 150 m². 2 The specific surface area (N2SA) of carbon black and / or nitrogen adsorption per gram is 110–220 m². 2 The product contains 50-90 parts by weight of silica-based inorganic filler per gram, further comprising the aforementioned crosslinking agent (B).

[0341] The performance requirements and mixing conditions for tire bead filler are the same as those for tire sidewalls, but particular emphasis is placed on fuel efficiency and tensile strength. Due to the characteristics of the components, tire bead filler requires a tensile strength no lower than that of tire sidewalls.

[0342] As described above, since the rubber-like polymer (A) is a polymer with a certain iodine value (10-250 (g / 100g)), the cross-linked body forms a uniform structure, and the tensile strength is improved.

[0343] Furthermore, the bead filler of a tire requires a higher proportion of compound than the filler in the tire sidewall, and to achieve higher hardness, it is often specially blended with thermosetting resins and curing agents. Therefore, to ensure good compounding processability, it tends to contain more natural rubber than the tire sidewall. Specifically, by ensuring a natural rubber content of 40 parts by mass or more per 100 parts by mass of the total rubber component, good processability during compounding can be ensured, and a good balance of physical properties can be achieved.

[0344] [use]

[0345] The crosslinking rubber composition of this embodiment is suitable as a material for the various tire components described above, and can also be used in other automotive interior and exterior parts, shock-absorbing rubber, belts, footwear (especially outsoles and midsoles), foams, and materials for various industrial products.

[0346] Among these, materials used for tire components are preferred.

[0347] As a tire component, it can be applied to various parts of tires, such as the tread, tire body, sidewall, and bead, including fuel-efficient tires, all-season tires, high-performance tires, snow tires, and studless anti-skid tires. In particular, the crosslinking rubber composition of this embodiment exhibits excellent low fuel consumption and tensile strength after being vulcanized, making it suitable for use as a sidewall, rubber bead wrapping, steel belt coated rubber, and bead filler.

[0348] As a tire manufacturing method, common methods can be used. For example, components commonly used in tire manufacturing, such as the tire carcass layer, belt layer, and tread layer, selected from the group consisting of an uncured cross-linked rubber composition and cord fabric, are sequentially overlapped and glued onto a tire forming drum. The drum is then removed to form a green tire. Next, the green tire is heated and vulcanized using conventional methods, thereby manufacturing the desired tire (e.g., a pneumatic tire).

[0349] Example

[0350] The following specific embodiments and comparative examples are provided to further illustrate this implementation method in detail, but this implementation method is not limited to any of the following embodiments and comparative examples.

[0351] The various physical properties in the examples and comparative examples were determined by the methods shown below.

[0352] ((Physical Property 1) Molecular Weight and Molecular Weight Distribution)

[0353] <Measurement Condition 1>: Using a rubbery polymer as a sample, the chromatogram was determined using a GPC assay apparatus (trade name "HLC-8320GPC" manufactured by Tosoh Corporation) with three columns connected to a polystyrene-based gel as the packing material, and an RI detector (trade name "HLC8020" manufactured by Tosoh Corporation) was used according to the [determination conditions] below. Based on the calibration curve obtained using standard polystyrene, the weight-average molecular weight (Mw), number-average molecular weight (Mn), and molecular weight distribution (Mw / Mn) were determined.

[0354] [Measurement Conditions]

[0355] GPC measuring device: Tosoh Corporation, trade name "HLC-8320GPC"

[0356] Eluent: Contains THF (tetrahydrofuran) with 5 mmol / L triethylamine.

[0357] Guard column: "TSKguardcolumn SuperMP(HZ)-H" manufactured by Tosoh Corporation

[0358] Column: Connect three “TSKgel SuperMultiporeHZ-H” connectors manufactured by Tosoh Corporation.

[0359] Oven temperature: 40℃

[0360] Flow rate: 0.35 mL / min

[0361] Sample: Dissolve 10 mg of the test sample in 10 mL of THF to prepare the test solution. Inject 10 μL of the test solution into the GPC measuring device for measurement.

[0362] For all samples measured using <Measurement Condition 1> above, samples with a molecular weight distribution (Mw / Mn) value less than 1.6 should be measured using <Measurement Condition 2> below, and the measurement results should be used. For samples measured using <Measurement Condition 1> with a molecular weight distribution value greater than or equal to 1.6, the measurement results of <Measurement Condition 1> should be used.

[0363] <Measurement Condition 2>: Using a rubbery polymer as a sample, the chromatogram was determined using a GPC assay apparatus (trade name "HLC-8320GPC" manufactured by Tosoh Corporation) with three columns connected to a polystyrene-based gel as the packing material, and an RI detector (trade name "HLC8020" manufactured by Tosoh Corporation) was used according to the [determination conditions] below. Based on the calibration curve obtained using standard polystyrene, the weight-average molecular weight (Mw), number-average molecular weight (Mn), and molecular weight distribution (Mw / Mn) were determined.

[0364] [Measurement Conditions]

[0365] GPC measuring device: Tosoh Corporation, trade name "HLC-8320GPC"

[0366] Eluent: THF containing 5 mmol / L triethylamine was added.

[0367] Protective column: "TSKguardcolumn SuperH-H" manufactured by Tosoh Corporation

[0368] Column: A column formed by sequentially connecting "TSKgel SuperH5000", "TSKgel SuperH6000" and "TSKgel SuperH7000" manufactured by Tosoh Co., Ltd. from upstream.

[0369] Oven temperature: 40℃

[0370] Flow rate: 0.6 mL / min

[0371] Sample: Dissolve 10 mg of the test sample in 20 mL of THF to prepare the test solution, and inject 20 μL of the test solution into the GPC test device for measurement.

[0372] ((Property 2) Mooney viscosity of rubbery polymers)

[0373] Using a rubbery polymer as a sample, the Mooney viscosity was determined according to ISO 289 using a Mooney viscometer (trade name "VR1132" manufactured by Uejima Seisakusho Co., Ltd.).

[0374] After preheating the sample at 100℃ for 1 minute, the L-shaped rotor was rotated at 2 rpm, and the torque was measured after 4 minutes to obtain the Mooney viscosity (ML). (1+4) ).

[0375] ((Physical Property 3) Modification Rate)

[0376] The modification rate of a rubbery polymer was determined using the column adsorption GPC method as follows. The rubbery polymer was used as a sample, and the modification rate was determined by utilizing the characteristic that the modified alkaline polymer components are adsorbed by a GPC column filled with silica-based gel.

[0377] The amount of adsorption on the silica column is determined by the difference between the chromatogram obtained by measuring the sample solution containing the sample and the low molecular weight internal standard polystyrene using a polystyrene column and the chromatogram obtained by measuring the sample solution using a silica column, and the modification rate is calculated.

[0378] For samples whose molecular weight distribution value is 1.6 or higher after testing under the above-described (property 1) test conditions 1, the test shall be conducted under the following test conditions 3, and the test results shall be used. For samples whose molecular weight distribution value is less than 1.6, the test shall be conducted under the following test conditions 4, and the test results shall be used.

[0379] <Determination Condition 3: GPC Determination Conditions Using Polystyrene Columns>: GPC measuring device: Tosoh Corporation, trade name "HLC-8320GPC" Eluent: THF containing 5 mmol / L triethylamine was added. Guard column: "TSKguardcolumn SuperMP(HZ)-H" manufactured by Tosoh Corporation Column: Connect three “TSKgel SuperMultiporeHZ-H” connectors manufactured by Tosoh Corporation.

[0380] Oven temperature: 40℃

[0381] Flow rate: 0.35 mL / min

[0382] RI detector (HLC8020 manufactured by Tosoh Corporation)

[0383] Sample: Dissolve 10 mg of the test sample and 5 mg of standard polystyrene in 20 mL of THF to prepare the test solution, and inject 10 μL of the test solution into the GPC test device.

[0384] <Determination Condition 4: GPC Determination Conditions Using Polystyrene Columns>: GPC measuring device: Tosoh Corporation, trade name "HLC-8320GPC" Eluent: THF containing 5 mmol / L triethylamine was added. Protective column: "TSKguardcolumn SuperH-H" manufactured by Tosoh Corporation Column: A column formed by sequentially connecting "TSKgel SuperH5000", "TSKgel SuperH6000" and "TSKgel SuperH7000" manufactured by Tosoh Co., Ltd. from upstream. Oven temperature: 40℃ Flow rate: 0.6 mL / min RI detector (HLC8020 manufactured by Tosoh Corporation) Sample: Dissolve 10 mg of the sample to be measured in 20 mL of THF to prepare the test solution. Inject 20 μL of the test solution into the GPC measuring device for measurement.

[0385] <GPC determination conditions using silica-based columns>: GPC measuring device: Tosoh Corporation, trade name "HLC-8320GPC" Elution buffer: THF Protective post: "DIOL 4.6×12.5mm 5micron" Column: A column formed by connecting "Zorbax PSM-1000S", "PSM-300S" and "PSM-60S" sequentially from upstream. Oven temperature: 40℃ Flow rate: 0.5 mL / min RI detector (HLC8020 manufactured by Tosoh Corporation) Sample: Dissolve 10 mg of the test sample and 5 mg of standard polystyrene in 20 mL of THF to prepare the test solution. Inject 50 μL of the test solution into the GPC test device.

[0386] <Method for calculating modification rate>: Set the peak area of ​​the chromatogram obtained using a polystyrene column to 100 for all values, and calculate the peak area P1 of the sample and the peak area P2 of the standard polystyrene. Similarly, set the peak area of ​​the chromatogram obtained using a silica column to 100 for all values, and calculate the peak area P3 of the sample and the peak area P4 of the standard polystyrene. Then, calculate the modification rate (%) based on the obtained area values ​​using the following formula.

[0387] Modification rate (%) = [1 - (P2 × P3) / (P1 × P4)] × 100

[0388] (Where, P1 + P2 = P3 + P4 = 100)

[0389] ((Property 4) Amount of styrene bound)

[0390] The rubber-like polymer was used as the sample. 100 mg of the sample was diluted to 100 mL with chloroform and dissolved to prepare the test sample.

[0391] The amount of styrene bound (mass%) relative to 100% by mass of the rubbery polymer used as the sample was determined by measuring the amount of styrene absorbed by the phenyl group of styrene at an ultraviolet absorption wavelength (around 254 nm) (measuring apparatus: Shimadzu UV-2450 spectrophotometer).

[0392] ((Physical Property 5) Microstructure of the butadiene moiety (1,2-vinyl binding content))

[0393] The rubber-like polymer was used as the sample. 50 mg of the sample was dissolved in 10 mL of carbon disulfide to prepare the test sample.

[0394] Using a solution dish, at a depth of 600–1000 cm. -1 The infrared spectrum was measured within a specified range. The microstructure of the butadiene moiety, i.e., the 1,2-vinyl binding amount (mol%), was determined from the absorbance at a specified wavenumber according to the calculation formula of the Hampton method (RRHampton, Analytical Chemistry 21, 923 (1949)). (Measurement device: Fourier transform infrared spectrophotometer "FT-IR230" manufactured by Nippon Spectrophotometer Co., Ltd.).

[0395] It should be noted that the "content of vinyl units and butene units" before hydrogenation is equivalent to the "1,2-vinyl binding amount," and the values ​​are the same. Therefore, the "content of vinyl units and butene units" in Tables 1-3 is equivalent to the 1,2-vinyl binding amount before hydrogenation.

[0396] ((Physical Property 6) Hydrogenation rate of rubber-like polymers, ethylene structure of rubber-like polymers, and content of vinyl and butene units)

[0397] Using a rubber-like polymer as a sample, through... 1 H-NMR determination was used to determine the hydrogenation rate, ethylene structure, and content of vinyl and butene units in rubber-like polymers.

[0398] 1 The H-NMR measurement conditions are as follows.

[0399] <Measurement Conditions>

[0400] Measuring instrument: JNM-LA400 (manufactured by JEOL)

[0401] Solvent: Deuterated chloroform

[0402] Sample tested: Rubber-like polymer

[0403] Sample concentration: 50 mg / mL

[0404] Observation frequency: 400MHz

[0405] Chemical shift reference: TMS (tetramethylsilane)

[0406] Pulse delay: 2.904 seconds

[0407] Number of scans: 64

[0408] Pulse width: 45°

[0409] Measurement temperature: 26℃

[0410] ((Physical Property 7) Styrene Block Content of Rubber-like Polymers)

[0411] A chain consisting of eight or more styrene structural units is considered a styrene block, and the amount of styrene blocks is calculated as follows.

[0412] Using deuterated chloroform as a solvent, the 1H-NMR spectrum of the rubber-like polymer was measured at 400 MHz. Based on the above spectrum, the integral ratio of (X) in each chemical shift range was calculated, and the amount of styrene block contained in the rubber-like polymer was determined.

[0413] Aromatic vinyl compounds with 8 or more chains: 6.00 ≤ x < 6.68

[0414] ((Property 8) Iodine value of rubbery polymers)

[0415] Using a rubbery polymer as a sample, the sample was dissolved in cyclohexane, and then iodine monochloride solution was added. The mixture was placed in a dark room, and then potassium iodide and water were added. The solution was titrated with sodium thiosulfate solution. When the solution turned pale yellow, starch solution was added, and titration was continued until the blue color disappeared. The iodine value was then determined.

[0416] ((Property 9) Glass transition temperature (Tg) of rubbery polymers)

[0417] Using a rubbery polymer as a sample, and in accordance with ISO 22768:2006, a differential scanning calorimeter "DSC3200S" manufactured by Mac Science was used to record the DSC curve while heating from -100°C at a rate of 20°C / min with a flow of 50 mL / min of helium. The peak (inflection point) of the DSC differential curve was taken as the glass transition temperature (Tg).

[0418] ((Physical Property 10) Calculation of SP value for rubbery polymers)

[0419] Based on ((molar cohesive energy) / (molar volume)) 1 / 2 The formula calculates the SP value (MPa) of the rubber-like polymer. 1 / 2 Tables 1-3 show the calculation of SP values.

[0420] Here, when the rubbery polymer is composed of two or more different monomers, the additivity of molar cohesive energies holds. The molar cohesive energy of the polymer is calculated as the average of the molar cohesive energies of each monomer (an average value proportionally distributed according to their content) based on the content (molar %) of each monomer and the molar cohesive energy of the homopolymer of that monomer.

[0421] Regarding molar volume, the same additive property applies as with molar cohesive energy. The molar volume of the polymer is calculated based on the content (mol%) of each monomer and the molar volume of the homopolymer of that monomer, expressed as the average molar volume of each monomer (an average proportionally distributed according to their content).

[0422] It should be noted that the molar cohesive energy and molar volume of the homopolymer composed of each monomer are shown below.

[0423] <Polyethylene homopolymer>

[0424] Molar cohesive energy: 36,932 (J / mol)

[0425] Molar volume: 97.0 (×10) -6 m 3 / mol)

[0426] <1,2-Polybutadiene homopolymer>

[0427] Molar cohesive energy: 16,450 (J / mol)

[0428] Molar volume: 58.3 (×10) -6 m 3 / mol)

[0429] <1,4-Polybutadiene homopolymer>

[0430] Molar cohesive energy: 18,579 (J / mol)

[0431] Molar volume: 59.1 (×10) -6 m 3 / mol)

[0432] <1,2-Polybutene homopolymer>

[0433] Molar cohesive energy: 17,527 (J / mol)

[0434] Molar volume: 65.6 (×10) -6 m 3 / mol)

[0435] <Polyethylene (1,4-hydrogenated polybutadiene) homopolymer>

[0436] Molar cohesive energy: 18,146 (J / mol)

[0437] Molar volume: 64.4 (×10) -6 m 3 / mol)

[0438] [Manufacturing of rubber-like polymers]

[0439] (Preparation of hydrogenation catalyst)

[0440] One liter of dried and purified cyclohexane was added to a reaction vessel purged with nitrogen, along with 100 mmol of bis(n5-cyclopentadiene)titanium dichloride. While stirring thoroughly, a solution of n-hexane containing 200 mmol of trimethylaluminum was added, and the reaction was carried out at room temperature for about 3 days to obtain the hydrogenation catalyst (TC-1).

[0441] (Example 1: Rubber-like polymer 1)

[0442] A 40L autoclave equipped with a stirrer and jacket, and capable of temperature control, was used as the reactor. 2,700g of 1,3-butadiene, 300g of styrene, 21,000g of cyclohexane (pre-removed impurities), 30mmol of tetrahydrofuran (THF) and 11.6mmol of 2,2-bis(2-tetrahydrofuranyl)propane (as polar substances) were added to the reactor, and the reactor temperature was maintained at 43°C.

[0443] 68.0 mmol of n-butyllithium, used as a polymerization initiator, was supplied to the reactor described above.

[0444] After the polymerization reaction began, the temperature inside the reactor started to rise due to the exothermic reaction, eventually reaching 76°C. Two minutes after reaching this peak temperature, 13.6 mmol of 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silazopentane (compound 1) was added to the reactor, and a coupling reaction was carried out for 20 minutes. 13.3 mmol of methanol was added to the polymer solution as a reaction terminator. A portion of the unhydrogenated rubbery polymer solution was extracted for analysis, and the solvent was removed using a dryer to obtain the unhydrogenated rubbery polymer.

[0445] Subsequently, the aforementioned hydrogenation catalyst (TC-1) was added to the unhydrogenated rubbery polymer solution at a concentration of 70 ppm (based on titanium) relative to 100 parts by mass of the unhydrogenated rubbery polymer. The hydrogenation reaction was carried out for 40 minutes at a hydrogen pressure of 0.8 MPa and an average temperature of 85 °C to obtain rubbery polymer 1. The iodine value of the obtained rubbery polymer 1 was 108.

[0446] 12.6 g of n-octadecyl-3-(3,5-di-tert-butyl-4-hydrogenated hydroxyphenyl)-propionate as an antioxidant and 3.0 g of 4,6-bis(octylthiomethyl)o-cresol were added to the solution of the obtained rubbery polymer 1, and the solution was dried.

[0447] The results of the analysis are shown in Table 1.

[0448] (Polymerization Examples 2 and 3) Rubber-like Polymers 2 and 3)

[0449] Except for making the hydrogenation reaction last for 60 minutes, rubber-like polymer 2 was obtained using the same method as described above (polymerization example 1).

[0450] Except for making the hydrogenation reaction last for 80 minutes, rubber-like polymer 3 was obtained using the same method as described above (polymerization example 1).

[0451] The iodine value of the obtained rubber-like polymer 2 is 65, and the iodine value of the obtained rubber-like polymer 3 is 22.

[0452] The results of the analysis are shown in Table 1.

[0453] (Example 4: Rubber-like polymer)

[0454] A 40L autoclave equipped with a stirrer and jacket, and capable of temperature control, was used as the reactor. 3,000g of 1,3-butadiene, 21,000g of cyclohexane, 30mmol of tetrahydrofuran (THF) (as a polar substance), and 8.9mmol of 2,2-bis(2-tetrahydrofuranyl)propane were added to the reactor, and the reactor temperature was maintained at 43°C.

[0455] 49.2 mmol of n-butyllithium, used as a polymerization initiator, was supplied to the reactor described above.

[0456] After the polymerization reaction began, the temperature inside the reactor started to rise due to the exothermic reaction, eventually reaching 78°C. Two minutes after reaching this peak temperature, 9.8 mmol of 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silazopentane (compound 1) was added to the reactor, and a coupling reaction was carried out for 20 minutes. 9.3 mmol of methanol was added to the polymer solution as a reaction terminator. A portion of the unhydrogenated rubbery polymer solution was extracted for analysis, and the solvent was removed using a dryer to obtain the unhydrogenated rubbery polymer.

[0457] Subsequently, the aforementioned hydrogenation catalyst (TC-1) was added to the unhydrogenated rubbery polymer solution at a concentration of 70 ppm (based on titanium) relative to 100 parts by mass of the unhydrogenated rubbery polymer. The hydrogenation reaction was carried out for 60 minutes at a hydrogen pressure of 0.8 MPa and an average temperature of 85 °C to obtain rubbery polymer 4. The iodine value of the obtained rubbery polymer 4 was 137.

[0458] 12.6 g of n-octadecyl-3-(3,5-di-tert-butyl-4-hydrogenated hydroxyphenyl)-propionate as an antioxidant and 3.0 g of 4,6-bis(octylthiomethyl)o-cresol were added to the solution of the obtained rubbery polymer 4, and the solution was dried.

[0459] The results of the analysis are shown in Table 1.

[0460] (Example 5: Rubber-like polymer)

[0461] A 40L autoclave equipped with a stirrer and jacket, and capable of temperature control, was used as the reactor. 3,000g of 1,3-butadiene, 21,000g of cyclohexane, 30mmol of tetrahydrofuran (THF) and 2.7mmol of 2,2-bis(2-tetrahydrofuranyl)propane (as polar substances) were added to the reactor, and the reactor temperature was maintained at 41°C.

[0462] 54.8 mmol of n-butyllithium, used as a polymerization initiator, was supplied to the reactor described above.

[0463] After the polymerization reaction began, the temperature inside the reactor started to rise due to the exothermic reaction, eventually reaching 78°C. Two minutes after reaching this peak temperature, 11.0 mmol of 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silazopentane (compound 1) was added to the reactor, and a coupling reaction was carried out for 20 minutes. 10.4 mmol of methanol was added to the polymer solution as a reaction terminator. A portion of the unhydrogenated rubbery polymer solution was extracted for analysis, and the solvent was removed using a dryer to obtain the unhydrogenated rubbery polymer.

[0464] Subsequently, the aforementioned hydrogenation catalyst (TC-1) was added to the unhydrogenated rubbery polymer solution at a concentration of 70 ppm (based on titanium) relative to 100 parts by mass of the unhydrogenated rubbery polymer. The hydrogenation reaction was carried out for 80 minutes at a hydrogen pressure of 0.8 MPa and an average temperature of 85 °C to obtain rubbery polymer 5. The iodine value of the obtained rubbery polymer 5 was 33.

[0465] 12.6 g of n-octadecyl-3-(3,5-di-tert-butyl-4-hydrogenated hydroxyphenyl)-propionate as an antioxidant and 3.0 g of 4,6-bis(octylthiomethyl)o-cresol were added to the solution of the obtained rubbery polymer 5, and the solution was dried.

[0466] The results of the analysis are shown in Table 1.

[0467] (Example 6: Rubber-like polymer)

[0468] The amount of 2,2-bis(2-tetrahydrofuranyl)propane added was 1.5 mmol, and the hydrogenation reaction was carried out for 20 minutes. Otherwise, the rubber-like polymer 6 was obtained by the same method as described above (polymerization example 1).

[0469] The iodine value of the obtained rubbery polymer 6 is 238.

[0470] The results of the analysis are shown in Table 1.

[0471] (Example 7: Rubber-like Polymer 7)

[0472] Except for making the hydrogenation reaction last for 60 minutes, rubber-like polymer 7 was obtained using the same method as described above (polymerization example 6).

[0473] The iodine value of the obtained rubbery polymer 7 is 65.

[0474] The results of the analysis are shown in Table 1.

[0475] (Example 8: Rubber-like polymer)

[0476] The amount of 2,2-bis(2-tetrahydrofuranyl)propane added was 25.0 mmol, and the hydrogenation reaction was carried out for 30 minutes. Otherwise, the rubber-like polymer 8 was obtained by the same method as described above (polymerization example 1).

[0477] The iodine value of the obtained rubbery polymer 8 is 173.

[0478] The results of the analysis are shown in Table 1.

[0479] (Polymerization Example 9) Rubber-like Polymer 9)

[0480] Except for the addition of 2,640 g of 1,3-butadiene, 360 g of styrene, 54.8 mmol of n-butyllithium, 5.0 mmol of 2,2-bis(2-tetrahydrofuranyl)propane, 11.0 mmol of 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silazopentane (compound 1) and 10.7 mmol of methanol, a rubbery polymer 9 was obtained using the same method as described above (polymerization example 1).

[0481] The iodine value of the obtained rubbery polymer 9 is 124.

[0482] The results of the analysis are shown in Table 1.

[0483] (Polymerization Example 10) Rubber-like Polymer 10)

[0484] Except that the amounts of added n-butyllithium 75.0 mmol, 2,2-bis(2-tetrahydrofuranyl)propane 6.5 mmol, 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silazopentane (compound 1) 15.0 mmol, methanol 14.6 mmol, and the hydrogenation reaction was carried out for 20 minutes, rubbery polymer 10 was obtained using the same method as described above (polymerization example 4).

[0485] The iodine value of the obtained rubbery polymer 10 is 235.

[0486] The results of the analysis are shown in Table 1.

[0487] (Polymerization Example 11) Rubber-like Polymer 11)

[0488] Except for making the hydrogenation reaction last for 60 minutes, rubber-like polymer 11 was obtained using the same method as described above (polymerization example 10).

[0489] The iodine value of the obtained rubbery polymer 11 is 71.

[0490] The results of the analysis are shown in Table 2.

[0491] (Polymerization Example 12) Rubber-like Polymer 12)

[0492] Except that the amounts of 1,3-butadiene 2,550 g, styrene 450 g, n-butyllithium 70.0 mmol, 2,2-bis(2-tetrahydrofuranyl)propane 20.0 mmol, 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silazopentane (compound 1) 14.0 mmol, methanol 13.6 mmol, and the hydrogenation reaction was carried out for 20 minutes, rubbery polymer 12 was obtained by the same method as described above (polymerization example 1).

[0493] The iodine value of the obtained rubbery polymer 12 is 200.

[0494] The results of the analysis are shown in Table 2.

[0495] (Polymerization Example 13) Rubber-like Polymer 13)

[0496] Except that the amounts of 1,3-butadiene 2,640 g, styrene 360 ​​g, and 2,2-bis(2-tetrahydrofuranyl)propane 25.0 mmol were added, rubber-like polymer 13 was obtained using the same method as described above (polymerization example 12).

[0497] The iodine value of the obtained rubbery polymer 13 is 248.

[0498] The results of the analysis are shown in Table 2.

[0499] (Polymerization Example 14) Rubber-like Polymer 14)

[0500] Except for the addition of 2,850 g of 1,3-butadiene, 150 g of styrene, 60.0 mmol of n-butyllithium, 35.0 mmol of 2,2-bis(2-tetrahydrofuranyl)propane, 12.0 mmol of 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silazopentane (compound 1) and 11.6 mmol of methanol, a rubbery polymer 14 was obtained using the same method as described above (polymerization example 1).

[0501] The iodine value of the obtained rubbery polymer 14 is 112.

[0502] The results of the analysis are shown in Table 2.

[0503] (Polymerization Example 15) Rubber-like Polymer 15)

[0504] Except for the addition of 2,940 g of 1,3-butadiene, 60 g of styrene, 70.0 mmol of n-butyllithium, 40.0 mmol of 2,2-bis(2-tetrahydrofuranyl)propane, 14.0 mmol of 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silazopentane (compound 1), and 13.6 mmol of methanol, a rubbery polymer 15 was obtained using the same method as described above (polymerization example 1).

[0505] The iodine value of the obtained rubbery polymer 15 is 138.

[0506] The results of the analysis are shown in Table 2.

[0507] (Polymerization Example 16) Rubber-like Polymer 16)

[0508] Except for adding 2,700 g of 1,3-butadiene, 300 g of styrene, 70.0 mmol of n-butyllithium, 50.0 mmol of 2,2-bis(2-tetrahydrofuranyl)propane, 14.0 mmol of 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silazopentane (compound 1), and 13.6 mmol of methanol, and for hydrogenation reaction time of 30 minutes, rubbery polymer 16 was obtained using the same method as described above (polymerization example 1).

[0509] The iodine value of the obtained rubbery polymer 16 is 169.

[0510] The results of the analysis are shown in Table 2.

[0511] (Example 17) Rubber-like polymer 17)

[0512] Except for making the hydrogenation reaction last for 80 minutes, rubber-like polymer 17 was obtained using the same method as described above (polymerization example 16).

[0513] The iodine value of the obtained rubbery polymer 17 is 21.

[0514] The results of the analysis are shown in Table 2.

[0515] (Example 18: Rubber-like polymer)

[0516] Except that the amounts of 1,3-butadiene 1,950 g, styrene 1,050 g, n-butyllithium 70.0 mmol, 2,2-bis(2-tetrahydrofuranyl)propane 30.0 mmol, 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silazopentane (compound 1) 14.0 mmol, methanol 13.6 mmol, and the hydrogenation reaction was carried out for 30 minutes, rubbery polymer 18 was obtained by the same method as described above (polymerization example 1).

[0517] The iodine value of the obtained rubbery polymer 18 is 122.

[0518] The results of the analysis are shown in Table 2.

[0519] (Polymerization Example 19) Rubber-like Polymer 19)

[0520] Except for making the hydrogenation reaction last for 80 minutes, rubber-like polymer 19 was obtained using the same method as described above (polymerization example 18).

[0521] The iodine value of the obtained rubbery polymer 19 is 15.

[0522] The results of the analysis are shown in Table 2.

[0523] (Polymerization Example 20) Rubber-like Polymer 20)

[0524] Except that the amounts of added materials were 95.0 mmol of n-butyllithium, 30.0 mmol of 2,2-bis(2-tetrahydrofuranyl)propane, 19.0 mmol of 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silazopentane (compound 1), and 18.5 mmol of methanol, a rubbery polymer 20 was obtained using the same method as described above (polymerization example 1).

[0525] The iodine value of the obtained rubbery polymer 20 is 108.

[0526] The results of the analysis are shown in Table 2.

[0527] (Polymerization Example 21) Rubber-like Polymer 21)

[0528] Except that the amounts of added butyllithium 15.0 mmol, tetrahydrofuran (THF) 10.0 mmol, 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silazopentane (compound 1) 3.0 mmol, methanol 2.9 mmol, and 2,2-bis(2-tetrahydrofuranyl)propane were not added, a rubbery polymer 21 was obtained using the same method as described above (polymerization example 1).

[0529] The iodine value of the obtained rubbery polymer 21 is 108.

[0530] The results of the analysis are shown in Table 3.

[0531] (Polymerization Example 22) Rubber-like Polymer 22)

[0532] Except that the amounts of 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silazopentane (compound 1) added were 7.6 mmol and methanol was 7.4 mmol, respectively, rubber-like polymer 22 was obtained using the same method as described above (polymerization example 1).

[0533] The iodine value of the obtained rubbery polymer 22 is 108.

[0534] The results of the analysis are shown in Table 3.

[0535] (Example 23: Rubber-like polymer 23)

[0536] Except that the amounts of 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silazopentane (compound 1) added were 10.2 mmol and methanol was 9.9 mmol, the same method as described above (polymerization example 1) was used to obtain rubbery polymer 23.

[0537] The iodine value of the obtained rubbery polymer 23 is 108.

[0538] The results of the analysis are shown in Table 3.

[0539] (Polymerization Example 24) Rubber-like Polymer 24)

[0540] Except that the amounts of added n-butyllithium 75.0 mmol, 2,2-bis(2-tetrahydrofuranyl)propane 16.0 mmol, methanol 9.7 mmol, and tris(3-trimethoxysilylpropyl)amine (compound 2) 10.0 mmol were used instead of 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silazopentane (compound 1), rubbery polymer 24 was obtained by the same method as described above (polymerization example 1).

[0541] The iodine value of the obtained rubbery polymer 24 is 108.

[0542] The results of the analysis are shown in Table 3.

[0543] (Polymerization Example 25) Rubber-like Polymer 25)

[0544] Except that the amounts of added butyllithium 82.0 mmol, 2,2-bis(2-tetrahydrofuranyl)propane 20.0 mmol, methanol 7.9 mmol, and tetra(3-trimethoxysilylpropyl)-1,3-diaminomethylcyclohexane (compound 3) 8.2 mmol were used instead of 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silazopentane (compound 1), a rubbery polymer 25 was obtained using the same method as described above (polymerization example 1).

[0545] The iodine value of the obtained rubbery polymer 25 is 108.

[0546] The results of the analysis are shown in Table 3.

[0547] (Polymerization Example 26) Rubber-like Polymer 26)

[0548] Except that the amounts of 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silazopentane (compound 1) added were 6.5 mmol and methanol was 6.3 mmol, respectively, rubber-like polymer 26 was obtained using the same method as described above (polymerization example 1).

[0549] The iodine value of the obtained rubbery polymer 26 is 108.

[0550] The results of the analysis are shown in Table 3.

[0551] (Polymerization Example 27) Rubber-like Polymer 27)

[0552] Except for the addition amounts of 1,800 g of 1,3-butadiene, 1,200 g of styrene, 60.0 mmol of n-butyllithium, 7.0 mmol of 2,2-bis(2-tetrahydrofuranyl)propane, 12.0 mmol of 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silazopentane (compound 1), and 11.6 mmol of methanol, a rubbery polymer 27 was obtained using the same method as described above (polymerization example 1).

[0553] The iodine value of the obtained rubbery polymer 27 is 71.

[0554] The results of the analysis are shown in Table 3.

[0555] (Polymerization Example 28) Rubber-like Polymer 28)

[0556] Except that the amounts of added n-butyllithium 60.0 mmol, tetrahydrofuran (THF) 20.0 mmol, 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silazopentane (compound 1) 12.0 mmol, methanol 11.6 mmol, and 2,2-bis(2-tetrahydrofuranyl)propane were not added, a rubbery polymer 28 was obtained using the same method as described above (polymerization example 1).

[0557] The iodine value of the obtained rubbery polymer 28 is 108.

[0558] The results of the analysis are shown in Table 3.

[0559] Compounds 1 to 3 in Tables 1 to 3 are shown below.

[0560] Compound 1: 2,2-Dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silazopentane

[0561] Compound 2: Tris(3-trimethoxysilylpropyl)amine

[0562] Compound 3: Tetra(3-trimethoxysilylpropyl)-1,3-diaminomethylcyclohexane

[0563] [Table 1]

[0564] [Table 2]

[0565] [Table 3]

[0566] [Rubber composition for tire sidewalls]

[0567] Examples 1-10, Examples 41-69, Comparative Example 1, and Comparative Examples 5-10

[0568] The following components are mixed to obtain a rubber composition.

[0569] More specifically, a closed mixing mill (0.5L capacity) equipped with a temperature control device is used as the first stage of mixing. The rubber components, reinforcing fillers, silane coupling agents, filler oils, stearic acid, anti-aging agents, and waxes are mixed under the conditions of a filling rate of 65% and a rotor speed of 50-90 rpm.

[0570] At this point, the temperature of the closed mixer is controlled, and the mixture is obtained at a discharge temperature of 150-160°C.

[0571] Next, as the second stage of mixing, the resulting mixture is cooled to room temperature and then mixed again to improve the dispersibility of the reinforcing filler. In this case, the discharge temperature of the mixture is also adjusted to 150–160°C by controlling the temperature of the mixer.

[0572] After cooling, as the third stage of mixing, zinc oxide, sulfidation accelerator and sulfur are added and mixed using an open mill set to 70°C.

[0573] It is then molded and vulcanized using a pressure vulcanizing machine at 160°C for 15–30 minutes.

[0574] The vulcanized rubber composition was evaluated using the following method.

[0575] The results of evaluations 1–4 are shown in Tables 4 and 8–13.

[0576] (The compounding material of the rubber composition used in the tire sidewall)

[0577] <Rubber Composition>

[0578] Rubber-like polymers 1-28: Rubber-like polymers obtained in the polymerization examples

[0579] NR: Natural Rubber RSS No. 3 (Producer: UNIMAC RUBBER CO., LTD. (Thailand), Supplier: Marubeni Techno Rubber)

[0580] BR: Polybutadiene rubber (manufactured by Ube Industries under the trade name "UBEPOL 150")

[0581] <Reinforcing filler>

[0582] Carbon black (manufactured by Tokai Carbon Co., Ltd., trade name "SEAST SO(FEF)", nitrogen adsorption specific surface area 42m²) 2 / g)

[0583] Silica (manufactured by Evonik Japan Degussa under the trade name "ULTRASIL 7000GR"), with a nitrogen adsorption specific surface area of ​​175 m². 2 / g)

[0584] <Silane coupling agent>

[0585] Silane coupling agent (trade name "Si75", manufactured by Evonik Japan Degussa Co., Ltd., bis(triethoxysilylpropyl) disulfide)

[0586] <Filling Oil>

[0587] Mineral oil: JXTG Energy manufactures "Process Oil PF30" (SRAE oil).

[0588] <Chemical Reagents>

[0589] Stearic acid (manufactured by Kao Corporation under the trade name "Lunac S-90V")

[0590] Anti-aging agent 6C (trade name "NOCRAC 6C" manufactured by Ouchi Shinsei Chemical Co., Ltd.)

[0591] Wax (manufactured by Ouchi Shinsei Chemical Co., Ltd. under the trade name "Sunnoc")

[0592] Zinc white

[0593] Zinc white (trade name "zinc oxide" manufactured by Sakai Chemical Industry Co., Ltd.)

[0594] <Vulcanization Accelerator>

[0595] DPG (1,3-diphenylguanidine) (manufactured by Ouchi Shinsei Chemical Co., Ltd. under the trade name "NOCCELER DP")

[0596] TBBS (N-tert-butylbenzothiazole-2-sulfenamide) (manufactured by Sanshin Chemical Co., Ltd. under the trade name "SancelerNS-G")

[0597] Sulfur

[0598] Powdered sulfur ("Sulfax 200S" manufactured by Tsurumi Chemical Industry Co., Ltd.)

[0599] [Rubber composition for rubber bead wrapping]

[0600] (Examples 11-20) and (Comparative Example 2)

[0601] The components described below are mixed to obtain a rubber composition.

[0602] Using a closed mixer (0.5L capacity) equipped with a temperature control device as the first stage of mixing, the rubber component, reinforcing filler, silane coupling agent, filler oil, resin, stearic acid, and anti-aging agent are mixed at a filling rate of 65% and a rotor speed of 50-90 rpm. During this process, the temperature of the closed mixer is controlled to achieve a discharge temperature of 150-160°C to obtain the final mixture.

[0603] Next, as the second stage of mixing, the resulting mixture is cooled to room temperature and then mixed again to improve the dispersibility of the reinforcing filler. In this case, the discharge temperature of the mixture is also adjusted to 150–160°C by controlling the temperature of the mixer.

[0604] After cooling, the third stage of mixing is carried out using an open mill set at 70°C, with the addition of zinc oxide, sulfidation accelerator and sulfur.

[0605] The rubber composition was then molded and vulcanized using a pressure vulcanizing machine at 150°C for 20–35 minutes. The vulcanized rubber composition was evaluated using the following method.

[0606] The results of Evaluation 1 and Evaluation 2 are shown in Table 5.

[0607] (The compounding material of the rubber composition used for rubber bead wrapping)

[0608] <Rubber Composition>

[0609] Rubber-like polymers 1-5: Rubber-like polymers obtained in the polymerization examples

[0610] NR: Natural Rubber RSS No. 3 (Producer: UNIMAC RUBBER CO., LTD. (Thailand), Supplier: Marubeni Techno Rubber)

[0611] BR: Polybutadiene rubber (trade name "UBEPOL 150" manufactured by Ube Industries, Ltd.)

[0612] <Reinforcing filler>

[0613] Carbon black (manufactured by Tokai Carbon Co., Ltd., trade name "SEAST KH(N339)", nitrogen adsorption specific surface area 93m²) 2 / g)

[0614] Silica (manufactured by Evonik Japan Degussa under the trade name "ULTRASIL 7000GR"), with a nitrogen adsorption specific surface area of ​​175 m². 2 / g)

[0615] <Silane coupling agent>

[0616] Silane coupling agent (trade name "Si75", manufactured by Evonik Japan Degussa Co., Ltd., bis(triethoxysilylpropyl) disulfide)

[0617] <Resin>

[0618] Alkylphenol-formaldehyde resin ("TACKIROL 130" manufactured by Taoka Chemical Co., Ltd.)

[0619] <Filling Oil>

[0620] Mineral oil: JXTG Energy manufactures "Process Oil PF30" (SRAE oil).

[0621] <Chemical Reagents>

[0622] Stearic acid (manufactured by Kao Corporation under the trade name "Lunac S-90V")

[0623] Anti-aging agent 6C (trade name "NOCRAC 6C" manufactured by Ouchi Shinsei Chemical Co., Ltd.)

[0624] Zinc white

[0625] Zinc white (trade name "zinc oxide" manufactured by Sakai Chemical Industry Co., Ltd.)

[0626] <Vulcanization Accelerator>

[0627] DPG (1,3-diphenylguanidine) (manufactured by Ouchi Shinsei Chemical Co., Ltd. under the trade name "NOCCELER DP")

[0628] TBBS (N-tert-butylbenzothiazole-2-sulfenamide) (manufactured by Sanshin Chemical Co., Ltd. under the trade name "SancelerNS-G")

[0629] Sulfur

[0630] Powdered sulfur ("Sulfax 200S" manufactured by Tsurumi Chemical Industry Co., Ltd.)

[0631] [Rubber composition for steel strip coated rubber]

[0632] (Examples 21-30) and (Comparative Example 3)

[0633] The components described below are mixed to obtain a rubber composition.

[0634] Using a closed mixer (0.5L capacity) equipped with a temperature control device as the first stage of mixing, the rubber component, reinforcing filler, silane coupling agent, filler oil, zinc oxide, anti-aging agent, and cobalt salt are mixed at a filling rate of 65% and a rotor speed of 50-90 rpm. During this process, the temperature of the closed mixer is controlled to obtain the various mixtures at a discharge temperature of 150-160°C.

[0635] Next, as the second stage of mixing, the resulting mixture is cooled to room temperature and then mixed again to improve the dispersibility of the reinforcing filler. In this case, the discharge temperature of the mixture is also adjusted to 150–160°C by controlling the temperature of the mixer.

[0636] After cooling, as the third stage of mixing, zinc white, vulcanization accelerator and insoluble sulfur are added and mixed using an open mill set to 70°C.

[0637] The rubber composition was then molded and vulcanized using a pressure vulcanizing machine at 150°C for 20–40 minutes. The vulcanized rubber composition was evaluated using the following method.

[0638] The results of Evaluation 1 and Evaluation 2 are shown in Table 6.

[0639] (A compounding material for rubber compositions used in steel strip coating)

[0640] <Rubber Composition>

[0641] Rubber-like polymers 1-5: Rubber-like polymers obtained in the polymerization examples

[0642] NR: Natural Rubber RSS No. 3 (Producer: UNIMAC RUBBER CO., LTD. (Thailand), Supplier: Marubeni Techno Rubber)

[0643] <Reinforcing filler>

[0644] Carbon black (manufactured by Tokai Carbon Co., Ltd., trade name "SEAST KH(N339)", nitrogen adsorption specific surface area 93m²) 2 / g))

[0645] Silica (manufactured by Evonik Japan Degussa under the trade name "ULTRASIL 7000GR"), with a nitrogen adsorption specific surface area of ​​175 m². 2 / g)

[0646] <Silane coupling agent>

[0647] Silane coupling agent (trade name "Si75", manufactured by Evonik Japan Degussa Co., Ltd., bis(triethoxysilylpropyl) disulfide)

[0648] <Filling Oil>

[0649] Mineral oil: JXTG Energy manufactures "Super Oil Y-22" (spindle oil).

[0650] <Chemical Reagents>

[0651] Zinc white (trade name "zinc oxide" manufactured by Sakai Chemical Industry Co., Ltd.)

[0652] Anti-aging agent 6C (trade name "NOCRAC 6C" manufactured by Ouchi Shinsei Chemical Co., Ltd.)

[0653] Anti-aging agent TMQ (trade name "NOCRAC 224" manufactured by Ouchi Shinsei Chemical Co., Ltd.)

[0654] Cobalt salt (manufactured by OMG under the trade name "Manobond C22.5")

[0655] Zinc white

[0656] Zinc white (trade name "zinc oxide" manufactured by Sakai Chemical Industry Co., Ltd.)

[0657] <Vulcanization Accelerator>

[0658] DPG (1,3-diphenylguanidine) (manufactured by Ouchi Shinsei Chemical Co., Ltd. under the trade name "NOCCELER DP")

[0659] CBS (N-cyclohexyl-2-benzothiazolyl sulfenamide) (manufactured by Ouchi Shinsei Chemical Co., Ltd. under the trade name "NOCCELER CZ-G")

[0660] <Insoluble sulfur>

[0661] Insoluble sulfur (Mucron OT-20 manufactured by Shikoku Chemical Co., Ltd.)

[0662] [Rubber composition for tire bead filler]

[0663] (Examples 31-40) and (Comparative Example 4)

[0664] The components described below are mixed to obtain a rubber composition.

[0665] Using a closed mixer (0.5L capacity) equipped with a temperature control device as the first stage of mixing, the rubber component, reinforcing filler, silane coupling agent, filler oil, resin, stearic acid, zinc oxide, and anti-aging agent are mixed at a filler ratio of 65% and a rotor speed of 50-90 rpm. During this process, the temperature of the closed mixer is controlled to obtain a compound at a discharge temperature of 150-160°C.

[0666] Next, as the second stage of mixing, the resulting mixture is cooled to room temperature and then mixed again to improve the dispersibility of the reinforcing filler. In this case, the discharge temperature of the mixture is also adjusted to 150–160°C by controlling the temperature of the mixer.

[0667] After cooling, the third stage of mixing is carried out using an open mill set to 70°C, with the addition of vulcanization accelerator, curing agent and insoluble sulfur.

[0668] The rubber composition was then molded and vulcanized at 160°C for 20–35 minutes using a pressure vulcanizing machine. The vulcanized rubber composition was evaluated using the following method.

[0669] The results of Evaluation 1 and Evaluation 2 are shown in Table 7.

[0670] (The compounding materials of the rubber composition used for bead filler)

[0671] <Rubber Composition>

[0672] Rubber-like polymers 1-5: Rubber-like polymers obtained in the polymerization examples

[0673] NR: Natural Rubber RSS No. 3 (Producer: UNIMAC RUBBER CO., LTD. (Thailand), Supplier: Marubeni Techno Rubber)

[0674] SBR: Styrene-butadiene rubber (trade name "Nipol 1502" manufactured by Zeon Corporation of Japan)

[0675] <Reinforcing filler>

[0676] Carbon black (manufactured by Tokai Carbon Co., Ltd., trade name "SEAST KH(N339)", nitrogen adsorption specific surface area 93m²) 2 / g)

[0677] Silica (manufactured by Evonik Japan Degussa under the trade name "ULTRASIL 7000GR"), with a nitrogen adsorption specific surface area of ​​175 m². 2 / g)

[0678] <Silane coupling agent>

[0679] Silane coupling agent (trade name "Si75", manufactured by Evonik Japan Degussa Co., Ltd., bis(triethoxysilylpropyl) disulfide)

[0680] <Resin>

[0681] Cashew nut shell oil modified phenolic resin (SUMITOMO BAKELITE's "SUMILIT Resin PR-NR-1")

[0682] <Filling Oil>

[0683] Mineral oil: JXTG Energy manufactures "Process Oil PF30" (SRAE oil).

[0684] <Chemical Reagents>

[0685] Stearic acid (manufactured by Kao Corporation under the trade name "Lunac S-90V")

[0686] Zinc white (trade name "zinc oxide" manufactured by Sakai Chemical Industry Co., Ltd.)

[0687] Anti-aging agent 6C (trade name "NOCRAC 6C" manufactured by Ouchi Shinsei Chemical Co., Ltd.)

[0688] <Vulcanization Accelerator>

[0689] DPG (1,3-diphenylguanidine) (manufactured by Ouchi Shinsei Chemical Co., Ltd. under the trade name "NOCCELER DP")

[0690] TBBS (N-tert-butylbenzothiazole-2-sulfenamide) (manufactured by Sanshin Chemical Co., Ltd. under the trade name "SancelerNS-G")

[0691] <Curing agent>

[0692] Hexamethylenetetramine (manufactured by Ouchi Shinsei Chemical Co., Ltd., under the trade name "NOCCELER H")

[0693] <Insoluble sulfur>

[0694] Insoluble sulfur (Mucron OT-20 manufactured by Shikoku Chemical Co., Ltd.)

[0695] [Evaluation of Rubber Compositions]

[0696] (Evaluation 1) Fuel efficiency

[0697] Using the obtained vulcanized rubber composition, the required test pieces were punched out, and the viscoelastic parameters were determined using the ARES viscoelastic testing machine manufactured by RheometricScientific in torsional vibration mode.

[0698] The tanδ measured at 50℃ with a frequency of 10Hz and a strain of 3% will be used as an indicator of low fuel consumption.

[0699] Use each measured value to summarize the measurement results.

[0700] In Table 4, the results for the rubber composition of Comparative Example 1 are marked as △; in Table 5, the results for the rubber composition of Comparative Example 2 are marked as △; in Table 6, the results for the rubber composition of Comparative Example 3 are marked as △; and in Table 7, the results for the rubber composition of Comparative Example 4 are marked as △. Cases where the effect is improved by 5% or more but less than 10% are marked as 0; cases where the effect is improved by 10% or more but less than 20% are marked as ◎; and cases where the effect is improved by 20% or more are marked as ◎◎.

[0701] In addition, cases where the effect improves or deteriorates by more than 0% but less than 5% are marked as △, cases where the effect deteriorates by more than 5% but less than 10% are marked as ×, and cases where the effect deteriorates by more than 10% are marked as ××.

[0702] (Evaluation 2) Mechanical Strength (Tensive Energy)

[0703] The tensile energy was evaluated using the obtained vulcanized rubber composition according to the test method shown below.

[0704] <Determination of Tensile Energy>

[0705] The obtained vulcanized rubber composition was punched into dumbbell-shaped test pieces according to JIS No. 3. Tensile tests were carried out at a tensile speed of 500 mm / min according to JIS K6251:2010. The stress-strain curve obtained was integrated from the strain at zero to the strain at fracture to determine the tensile energy.

[0706] Use each measured value to summarize the measurement results.

[0707] In Table 4, the results for the rubber composition of Comparative Example 1 are marked as △; in Table 5, the results for the rubber composition of Comparative Example 2 are marked as △; in Table 6, the results for the rubber composition of Comparative Example 3 are marked as △; and in Table 7, the results for the rubber composition of Comparative Example 4 are marked as △. An improvement of 5% or more but less than 10% is marked as 〇; an improvement of 10% or more but less than 20% is marked as ◎; and an improvement of 20% or more is marked as ◎◎. Furthermore, an improvement or deterioration of the effect of 0% or more but less than 5% is marked as △; a deterioration of the effect of 5% or more but less than 10% is marked as ×; and a deterioration of 10% or more is marked as ××.

[0708] (Evaluation 3) Ozone tolerance)

[0709] The ozone resistance of the obtained vulcanized rubber composition was evaluated using the test methods shown below.

[0710] <Evaluation of Ozone Tolerance>

[0711] Using a vulcanized rubber composition, vulcanization and pressure are applied at 160°C for 15–30 minutes using a specified mold (15cm length × 15cm width × 2.0mm thickness) to obtain vulcanized rubber sheets. Strip samples (6cm length × 1cm width × 2.0mm thickness) are punched from these sheets and placed in an ozone bath (50°C, 100pphm) and left to stand for 48 hours under 40% tension. The strip samples (vulcanized rubber sheets) are then observed, and the number of cracks longer than 1mm on the surface is counted and evaluated according to the following criteria.

[0712] The criteria and evaluation results are shown in Table 4 (Ozone Tolerance).

[0713] [Judgment Criteria]

[0714] ×: Broken vulcanized rubber sheet

[0715] △: There are 21 or more cracks larger than 1mm.

[0716] ○: Cracks larger than 1mm are defined as 10 to 20.

[0717] ◎: Cracks larger than 1mm are defined as 1 or more but less than 10.

[0718] ◎◎: No cracks larger than 1mm exist.

[0719] (Evaluation 4) Storage stability)

[0720] The raw materials specified in Tables 8 to 13 were mixed to obtain a compound, which was then vulcanized after 1 day, and the mechanical strength (tensile energy) of (Evaluation 2) was measured as described above. The result of this measurement is taken as (a).

[0721] In addition, the raw materials specified in Tables 8 to 13 were mixed to obtain a compound, which was then vulcanized after 7 days, and the above-mentioned mechanical strength (tensile energy) was measured (Evaluation 2). The result of this measurement is taken as (b).

[0722] Based on these results (a) and (b), an evaluation is conducted using the following criteria.

[0723] [Judgment Criteria]

[0724] ×: The difference between (a) and (b) is more than 20%.

[0725] △: The difference between (a) and (b) is more than 10% but less than 20%.

[0726] ○: The difference between (a) and (b) is 5% or more but less than 10%.

[0727] ◎: The difference between (a) and (b) is less than 5%.

[0728] [Table 4]

[0729] [Table 5]

[0730] [Table 6]

[0731] [Table 7]

[0732] [Table 8]

[0733] [Table 9]

[0734] [Table 10]

[0735] [Table 11]

[0736] [Table 12]

[0737] [Table 13]

[0738] This application incorporates, by reference, the contents of Japanese Patent Application No. 2021-001427 filed with the Japan Patent Office on January 7, 2021, and Japanese Patent Application No. 2021-065420 filed with the Japan Patent Office on April 7, 2021.

[0739] Industrial applicability

[0740] The crosslinking rubber composition of this embodiment has industrial applicability in fields such as tire parts, automotive interior and exterior parts, shock-absorbing rubber, belts, footwear, foams, and various industrial products.

Claims

1. A sheet comprising a crosslinkable rubber composition, wherein the crosslinkable rubber composition comprises: A rubbery polymer (A) having an iodine value of 10 g / 100g to 250 g / 100g, an ethylene structure content ≧ 3 mass%, a vinyl aromatic monomer block content of < 10 mass%, containing a nitrogen atom, a modification ratio measured by column adsorption GPC method of 40 mass% or more, a glass transition temperature of -60°C or lower, and a weight average molecular weight of 200,000 or more; and A crosslinking agent (B), The sheet contains a rubber component, and 100 parts by mass of the rubber component comprises 30 parts by mass or more of natural rubber, 10 parts by mass or more of butadiene rubber, and 10 parts by mass or more of the rubbery polymer (A), The SP value and the glass transition temperature Tg of the rubbery polymer (A) satisfy: (-0.03×Tg+14.4) < SP value < (-0.03×Tg+15.4), wherein, The iodine value is measured according to the method described in "JIS K 0070:1992", and the iodine value is a value expressed by converting the amount of halogen that reacts with 100 g of the target substance into the grams of iodine, The vinyl aromatic monomer block refers to a block formed by linking 8 or more vinyl aromatic monomer units, The modification ratio represents the mass proportion of the polymer having a nitrogen atom-containing functional group relative to the total amount of the rubbery polymer (A), The SP value is calculated by the formula (SP value) = ((molar cohesive energy) / (molar volume))1 / 2.

2. The sheet as described in claim 1, wherein, The rubbery polymer (A) contains 35 mass% or less of vinyl aromatic monomer units.

3. The sheet as described in claim 1 or 2, wherein, The content of vinyl units and butene units in the rubbery polymer (A) is 20 mol% or more.

4. The sheet as described in claim 1 or 2, wherein, The iodine value of the rubbery polymer (A) is 15 g / 100g to 200 g / 100g.

5. The sheet as described in claim 1 or 2, wherein, In the rubbery polymer (A), the ethylene structure content is 5 mass% or more and 70 mass% or less.

6. The sheet as described in claim 1 or 2, wherein, In the rubbery polymer (A), the vinyl aromatic monomer block content is 5 mass% or less.

7. The sheet as described in claim 1 or 2, wherein, The modification ratio of the rubbery polymer (A) measured by column adsorption GPC method is 60 mass% or more.

8. The sheet as described in claim 1 or 2, wherein, The glass transition temperature of the rubbery polymer (A) is -90°C or higher and -60°C or lower.

9. The sheet as described in claim 1 or 2, wherein, The hydrogenation ratio of the rubbery polymer (A) is 60 mol% to 95 mol%, The hydrogenation rate is obtained through 1 Measured by H-NMR. 1 The H-NMR measurement conditions are as follows: Measurement instrument: JNM-LA400 (manufactured by JEOL) Solvent: Deuterated chloroform Test sample: Rubbery polymer Sample concentration: 50 mg / mL Observation frequency: 400 MHz Chemical shift reference: TMS (tetramethylsilane) Pulse delay: 2.904 seconds Number of scans: 64 times Pulse width: 45° Measurement temperature: 26°C.

10. The sheet as claimed in claim 3, wherein, The content of vinyl units and butene units in the rubbery polymer (A) is 20 mol% or more and 60 mol% or less.

11. The sheet as described in claim 1 or 2, wherein, The Mooney viscosity of the rubbery polymer (A) measured at 100°C is 64 or more.

12. The sheet as claimed in claim 1, wherein, In 100 parts by mass of the rubber component, the content of the rubbery polymer (A) is 30 parts by mass or more.

13. The sheet as claimed in claim 1, wherein, Relative to 100 parts by mass of the rubber component, it further contains 50 to 90 parts by mass of a nitrogen adsorption specific surface area (N2SA) of 20 m². 2 / g~150m 2 The specific surface area of ​​carbon black and / or nitrogen adsorption (N2SA) is 110 m² / g. 2 / g~220m 2 / g of silica-based inorganic filler.

14. The sheet according to claim 1, which is a sheet for tire sidewalls.

15. The sheet as claimed in claim 13, wherein, The nitrogen adsorption specific surface area (N2SA) is 20 m² relative to 100 parts by mass of the rubber component. 2 / g~150m 2 The specific surface area of ​​carbon black and / or nitrogen adsorption (N2SA) is 110 m² / g. 2 / g~220m 2 The content of silica-based inorganic filler per g is more than 50 parts by weight and less than 80 parts by weight.

16. A method for manufacturing a tire sidewall, comprising the following steps: a step of kneading a crosslinkable rubber composition, natural rubber, and butadiene rubber such that the content of the natural rubber is 30 parts by mass or more, the content of the butadiene rubber is 10 parts by mass or more, and the content of the rubbery polymer (A) is 10 parts by mass or more, relative to 100 parts by mass of the rubber component; a step of forming into a sheet; and a step of crosslinking the obtained sheet-shaped formed body, wherein the crosslinkable rubber composition comprises: a rubbery polymer (A) having an iodine value of 10 g / 100g to 250 g / 100g, an ethylene structure content ≧3 mass%, a vinyl aromatic monomer block content <10 mass%, containing a nitrogen atom, a modification ratio measured by column adsorption GPC of 40 mass% or more, a glass transition temperature of -60°C or lower, and a weight average molecular weight of 200,000 or more; and a crosslinking agent (B), wherein the SP value and the glass transition temperature Tg of the rubbery polymer (A) satisfy: (-0.03×Tg+14.4) < SP value < (-0.03×Tg+15.4), wherein, the iodine value is measured according to the method described in "JIS K 0070:1992", and the iodine value is a value expressed by converting the amount of halogen that reacts with 100 g of the target substance into the number of grams of iodine, the vinyl aromatic monomer block refers to a block formed by linking 8 or more vinyl aromatic monomer units, the modification ratio represents the mass proportion of the polymer having a nitrogen atom-containing functional group relative to the total amount of the rubbery polymer (A), the SP value is calculated by the formula (SP value) = ((molar cohesive energy) / (molar volume))^1 / 2.

17. A tire sidewall comprising a rubber component, wherein 100 parts by mass of the rubber component comprises: 10 parts by mass or more of a rubbery polymer (A) having an iodine value of 10 g / 100g to 250 g / 100g, an ethylene structure content ≧3 mass%, a vinyl aromatic monomer block content <10 mass%, containing a nitrogen atom, a modification ratio measured by column adsorption GPC of 40 mass% or more, a glass transition temperature of -60°C or lower, and a weight average molecular weight of 200,000 or more; 30 parts by mass or more of natural rubber; and 10 parts by mass or more of butadiene rubber, wherein the SP value and the glass transition temperature Tg of the rubbery polymer (A) satisfy: (-0.03×Tg+14.4) < SP value < (-0.03×Tg+15.4), the tire sidewall has a structure formed by crosslinking the rubbery polymer (A), the natural rubber, and the butadiene rubber, wherein, the iodine value is measured according to the method described in "JIS K 0070:1992", and the iodine value is a value expressed by converting the amount of halogen that reacts with 100 g of the target substance into the number of grams of iodine, the vinyl aromatic monomer block refers to a block formed by linking 8 or more vinyl aromatic monomer units, the modification ratio represents the mass proportion of the polymer having a nitrogen atom-containing functional group relative to the total amount of the rubbery polymer (A), The SP value is calculated using the formula (SP value) = ((molar cohesive energy) / (molar volume))1 / 2.

18. The tire sidewall as claimed in claim 17, comprising: 100 parts by weight of a rubber component comprising 10 or more parts by weight of the rubbery polymer (A), 30 or more parts by weight of natural rubber and 10 or more parts by weight of butadiene rubber; 50-90 parts by mass of nitrogen adsorption specific surface area N2SA is 20m² 2 / g~150m 2 The specific surface area of ​​carbon black and / or nitrogen adsorption (N2SA) is 110 m² / g. 2 / g~220m 2 / g of silica-based inorganic filler; and Crosslinking agent (B).

19. The tire sidewall as claimed in claim 17, wherein, The iodine value of the rubbery polymer (A) is 15g / 100g to 200g / 100g.

20. The tire sidewall as claimed in claim 17, wherein, In the rubbery polymer (A), the ethylene structure is more than 5% by mass and less than 70% by mass.

21. The tire sidewall as claimed in claim 17, wherein, In the rubbery polymer (A), the vinyl aromatic monomer block is less than 5% by mass.

22. The tire sidewall as claimed in claim 17, wherein, The modification rate of the rubbery polymer (A) determined by column adsorption GPC method was more than 60% by mass.

23. The tire sidewall as claimed in claim 17, wherein, The hydrogenation rate of the rubbery polymer (A) is 60 mol% to 95 mol%. The hydrogenation rate is obtained through 1 Measured by H-NMR. 1 The H-NMR measurement conditions are as follows: Measuring instrument: JNM-LA400 (manufactured by JEOL) Solvent: Deuterated chloroform Sample tested: Rubber-like polymer Sample concentration: 50 mg / mL Observation frequency: 400MHz Chemical shift reference: TMS (tetramethylsilane) Pulse delay: 2.904 seconds Number of scans: 64 Pulse width: 45° Measurement temperature: 26℃.

24. The tire sidewall as claimed in claim 17, wherein, The content of vinyl units and butene units in the rubbery polymer (A) is more than 20 mol% and less than 60 mol%.

25. The tire sidewall as claimed in claim 17, wherein, The rubbery polymer (A) has a Mooney viscosity of 64 or higher when measured at 100°C.

26. The tire sidewall as claimed in claim 18, wherein, The content of the crosslinking agent (B) is 0.5 parts by mass or more and 5 parts by mass or less, relative to 100 parts by mass of the rubber component.

Citation Information

Patent Citations

  • Hydrogenated conjugated di olefin polymer

    JP2000053706A

  • Rubber composition and tire using the same

    JP2010270314A

  • Textile machine having a plurality of work units and method for monitoring textile machine having a plurality of work units

    JP2021001427A

  • Game machine

    JP2021065420A

  • Block copolymers containing both polystyrene and low vinyl content polydiene hard blocks

    WO2002002663A2